Simulation thermique pour l'habitat traditionnel et contemporain au M'Zab - Lane, Abir (Ecole Polytechnique d'Architecture et d'Urbanisme, 2020)

Le M'zab, une leçon patrimoniale - Zehar, Malek Zahida (Ecole Polytechnique d'Architecture et d'Urbanisme, 2020)

Beni Isguen, une référence patrimoniale pour repenser la conception d'un Ksar dans la vallée du Mzab - Ghemmar, Mahfoudh Idris (Ecole Polytechnique d'Architecture et d'Urbanisme, 2020)

Mise en élégance d'un Ksar du M'zab - Zellagui, Younes Islem (Ecole Polytechnique d'Architecture et d'Urbanisme, 2020)

Ksar de Bou Noura (Ghardaia), un support, une réflexion et un patrimoine élégant - Saidi, Radhia (Ecole Polytechnique d'Architecture et d'Urbanisme, 2020)

La maison de Ghardaia , une unité de modernisation de l'architecture vernaculaire Mozabite - Sedjal, Abdesselam (Ecole Polytechnique d'Architecture et d'Urbanisme, 2020)

La maison d'El Guerrara (Ghardaia) - Bouhzam, Hanane (Ecole Polytechnique d'Architecture et d'Urbanisme, 2020)

Amazighs (Berbères) de Libye : de la résistance à l’affirmation - Ferkal, Masin (Institut National des Langues et Civilisations Orientales, 2025)

Al-Jabal al–Akhḍar Revolution, 1955-1965: Rediscovering Oman's Anti-Colonial Resistance - Hashmi, Said Sultan Al (University of Houston, 2025)

Mécanisme de la sauvegarde de vieux Ksar Mlika : évaluation d’expérience - Houichiti, Salsabil; Bammoune, Zakaria (Université de Ghardaïa, 2025)
Keywords: Monuments -- conservation -- Mzab; Urbanisme -- Mzab

الفكر العقدي المعاصر عند إباضية الجزائر - أولاد يحي, فاطمة (جامعة الأمير عبد القادر للعلوم الاسلامية, 2025)

لإعلام الجواري ودوره في تعزيز قيم المواطنة: دراسة تحليلية لعينة من برامج إذاعة غرداية - وهاب, مسعود; حاج عمر, علي (جامعة غرداية, 2025)

Évaluation de quelques activités biologiques des extraits aqueux et polysaccharidiques de dattes (Phoenix dactylifera L.) de la région de Ghardaïa - Abdelaziz, Aissa; Abismail Hedjoudja, Nacer (Université de Ghardaia, 2025)
Keywords: Botanique -- Mzab

النظام العقابي في المجتمع الميزابي خلال القرن الخامس عشر إلى التاسع عشر الميلادي دراسة مقارنة بين الفقه الإسلامي وقانون العقوبات الجزائري - إزغار, يحي (جامعة أحمد درايعية, 2026)
Keywords: Justice -- Mzab

Patrimoine culturel, tourisme et acteurs locaux à Djerba. De 1960 jusqu'à nos jours - Elouati, Mehdi (Ecole des hautes études en sciences sociales, 2025)
La thèse se limite à l’île de Djerba au Sud-Est de la Tunisie, cette l'île a fait beaucoup parler d'elle, de son architecture, de son histoire, de sa diversité culturelle (artisanale, culinaire, linguistique, …) et ethnique (berbères, arabes, …), ainsi qu’un vivre ensemble rare entre juifs, musulmans (malékites et ibadites) et chrétiens (catholiques et orthodoxes). En réalité, le tourisme est devenu depuis 1960 l’activité principale de l’île, d’où l’intégration d’une grande partie de sa population dans cette activité. Cette thèse analyse la relation entre le tourisme et le patrimoine à Djerba, mais aussi le degré d’implication des acteurs locaux dans des processus de patrimonialisation et de mise en tourisme à partir des années soixante jusqu’à nos jours. Bien évidemment, la thèse évoque la Tunisie « postrévolutionnaire » qui a incarné un engagement citoyen sans précédent sur le plan national en général, et dans la mise en valeur du patrimoine en particulier. Durant cette période de transition, le pays a connu une réactivité sans précédent de la part des acteurs locaux et des associations venus joindre l’effort collectif, de louables actions culturelles dans les régions, sur le patrimoine, entre autres. Inévitablement, cette île a été marquée par un essor remarquable de l’activité associative depuis 2011 faisant du patrimoine un centre d’intérêt qu’il faut sauver, partager et intégrer dans la dynamique économique comme le projet d’inscription de l’île sur la liste du patrimoine mondial de l’Unesco.
Keywords: Tourisme -- Djerba

النظام العشائري في منطقة القبائل من خلال تنظيم تاجماعث: دراسة ميدانية بمنطقة تيزي وزو - زمور, غانبة (جامعة وهران 2, 2021)
Le système tribal dans la région Kabyle est représenté dans l’organisation de Tajmaath, la seule institution dirigeante dans le village kabyle. Cette structure coutumière a réussi à diriger le pouvoir de décision dans la région tout en réconciliant la dimension réelle du rôle joué par Tajmaath et l’adaptation entre la structure politique, sociale et économique de la société algérienne dans le cadre d’un ensemble strict de lois coutumières. Ces lois ont réglementé la vie sociale des villages prioritairement à travers plusieurs pratiques, et a imposé des sanctions qui varient selon la violation et son acteur, qui vont toutes en parallèle avec la loi positive algérienne, il n’y a par conséquent pas de droit coutumier qui affecte la constitution et vice versa .The tribal system in the Kabyle region is represented in the organization of Tajma'ath, the only ruling institution in the Kabyle village. This customary structure has managed to direct decision-making power in the region while reconciling the real dimension of the role played by Tajma'ath and the adaptation between the political structure, social and economic aspects of Algerian society within the framework of a strict set of customary laws. These laws have regulated the social life of villages primarily through several practices, and imposed sanctions that vary according to the violation and its actor, all of which go in parallel with the positive Algerian law, there is therefore no customary law that affects the constitution and vice versa. النظام العشائري في منطقة القبائل من خلال تنظيم تاجماعث _دراسة ميدانية بمنطقة تيزي وزو :الملخص يتجسد النظام العشائري بمنطقة القبائل في تنظيم تاجماعث الذي يعتبر المؤسسة الوحيدة الحاكمة في القرية القبائلية. فقد استطاعت هذه التركيبة العرفية أن تتحكم في سلطة القرار في المنطقة، وذلك من خلال التوفيق بين البعد الحقيقي للدور الذي تلعبه تاجماعث، والتأقلم بين البنية السياسية و الاجتماعية والاقتصادية للمجتمع الجزائري، تحت مجموعة قوانين عرفية صارمة. فقد عملت هذه الأخيرة على تنظيم الحياة الاجتماعية للقرى بدرجة أولى من خلال عدّة ممارسات، و فرض عقوبات تختلف حسب المخالفة و فاعلها، و كلّها تسير بالموازاة مع القانون الوضعي للجزائر، فلا قانون عرفي يمس بالدستور والعكس صحيح
Keywords: Tribalisme -- Kabylie

طقوس العبور (من الميلاد إلى الوفاة) والتحوّلات السوسيو ثقافية: المجتمع الشعانبي بمتليلي - ولاية غرداية نموذجا- دراسة سوسيوأنثروبولوجية - بوزيد, عائشة (جامعة وهران 2, 2024)
تهدف هذه الدراسة إلى حصر طقوس العبور في مجتمع الدراسة وتسميتها وتحديد الرمزي فيها والمقصد منها، ومن ثمة معرفة المتغير منها بعوامله السوسيو ثقافية المتحكمة فيه. وهنا تتضح أهمية الموضوع مقارنة بما قدمه فان جينيب عن بقية - المجتمعات. ولأن دراستنا إثنوغرافية فقد استعنا بالمنهج الكيفي ثم التاريخي، حيث خلصنا في النهاية أن للوعي الديني وتغير النمط الاقتصادي، كما التثاقف أثر في تغير طقوس العب ور بمتليلي. الكلمات المفتاحية: طقس، طقوس العبور، السوسيوثقافي، الوعي الديني، التثاقف، نمط الاقتصاد *** « Rites de passage (de la naissance à la mort) et transformations- société socioculturelle de Sha'anbi Metlili - modèle de l'État de Ghardaia- etude socio- anthropologique » Résumé: Le but de cette étude est de limiter les rites de passage dans la communauté d'étude, de les nommer, d'en déterminer le symbolisme et le but, et de là la connaissance variable de ses facteurs socioculturels qui la contrôlent.Et ici, l'importance du sujet devient claire par rapport à ce que van Gennep a présenté sur le reste des sociétés.Et parce que notre étude est ethnographique, nous avons utilisé l'approche qualitative puis historique, où nous avons finalement conclu que la conscience religieuse et le changement de modèle économique, ainsi que l'acculturation ont influencé le changement des rites de passage à Metlili. Mots clés: rite, rites de passage, socioculturel, conscience religieuse, acculturation, style économique
Keywords: Moeurs et coutumes -- Mzab

العلاقات الاجتماعية وتعزيز الاندماج الاجتماعي للتجار المزابيين في المجتمع المحلي (1962-2018) دراسة ميدانية بمدن الغرب الجزائري - لطروش, بلقاسم (جامعة وهران 2, 2025)
ملخص: تعالج هذه الأطروحة العلاقة بين العلاقات الاجتماعية التي ينسجها التاجر المزابي في منطقة الغرب الجزائري واندماجه في المجتمع المحلّي لكل مدينة، حيث يمثل النشاط التجاري مجالا اجتماعيا غنيا بالعلاقات الاجتماعية والمعاملات التجارية في المحيط الحضري الذي يحوز على سوق استهلاكية كبيرة. لقياس هذه العلاقة بين المتغيرين اعتمدنا على المزج بين المنهج الكمي والكيفي؛ من أجل الإحاطة الواسعة قدر الإمكان لمسار هجرة الجماعة المزابية من وادي ميزاب إلى مدن الغرب الجزائري وواقع العلاقة بين التاجر المزابي والرجل المحلّي، معتمدين في ذلك على الاستمارة والمقابلة لجمع المعلومات اللازمة لقياس هذه العلاقة، وكانت من أهم النتائج المتحصل عليها وجود علاقات صداقة وجيرة قوية بين الطرفين في المدينة، كما يوجد علاقة مصاهرة بين التاجر والمحلّي وأكثر من هذا مشاركة المزابي في نشاطات المجتمع المحلّي في منطقة الغرب الجزائري. Résumé: La thèse traite la relation entre les relations sociales que le commerçant Mozabite les ai tissé dans la région de l’Ouest algérien et son intégration dans la communauté locale de chaque ville, où l’activité commerciale est un espace social riche en relations sociales et transactions commerciales dans l’océan urbain qui détient un grand marché de consommation. Cette relation entre les deux variables nécessite une mesure scientifique, ou nous nous sommes appuyés sur une combinaison d’approches quantitatives et qualitatives ; Afin de capturer le plus largement possible le parcours migratoire de la communauté Mozabite de la vallée de M’Zab aux villes de l’Ouest algérien et la réalité de la relation entre le commerçant et l’individu local. En basant sur la technique du formulaire et l’entretien pour avoir des informations nécessaires afin examiner cette relation, l’un des résultats les plus importants obtenus a été l’existence de relations amicales et de bon voisinage entre les deux parties dans la ville. Il y a aussi un rapport entre le commerçant et le local où la participation du commerçant aux activités de la société locale dans la région algérienne occidentale est fort.
Keywords: Commerce -- Mzab; Emigration -- Mzab -- Algérie

Language Maintenance and language shift among the Berbers of Djerba (Southern Tunisia) - Bouhdima, Mohamed Elhedi (Université de Sfax, 2025)
Keywords: Linguistique -- Djerba

سيميولوجيا الصورة الفوتوغرافية حول العمران التقليدي بولاية غرداية - حمياني, عائشة (جامعة غرداية, 2025)
Keywords: Urbanisme -- Mzab

İbâzî Tefsir Geleneğinde Ahkâm Âyetlerinin Yorumu: Teysîrü't-Tefsîr Örneği - Ezber, Mahbup Zeynep (Istanbul Üniversitesi, 2025)
Araştırmanın amacı İbâzî tefsir geleneğinde ahkâm âyetlerinin nasıl yorumlandığını ortaya koymaktır. Bu amaç için incelenilen tefsir Muhammed b. Yûsuf Ettafeyyiş'in son tefsir eseri olan Teysîrü't-Tefsîr'dir. Nitekim Ettafeyyiş mezhebi içerisinde "Kutb" lakabı ile anılan tefsir ve fıkıh ilimleri başta olmak üzere diğer İslâmî ilimlerde de yetkinlik sahibi olan bir müfessirdir. Ettafeyyiş'in de eserinde vurguladığı gibi İbâzıyye mezhebi, Hanefî mezhebi ile ahkâma ait birçok konuda ittifak halindedir. Bunun yanı sıra Şâfîî ve Mâlikî mezhebi ile de birçok meselede ittifakı bulunan Ettafeyyiş eserinde bu benzerlikleri ifade ederken mezhepler ile ihtilaf halinde olduğu konuları da belirtmekten çekinmemiştir. Özellikle Zâhirî mezhebi ile olan ihtilafları, Ettafeyyiş'in ve mezhebinin âyetleri literal okumaktan uzak olduklarını ortaya koymaktadır. İbâzıyye mezhebinin neşet ettiği Hâricî mezhebi ile bir görüş birliği içerisinde olmaması gerek Ettafeyyiş'in gerek İbâzıyye'nin, Hâricîler gibi nasları yorumlamada sert bir tutuma sahip olmadıklarının göstergesidir. Her ne kadar İbâzıyye, Hâricî fırkaları arasından günümüze ulaşan tek zümre olsa da İbâzîler dinin ahkâmı karşısında literal tavırdan uzak durmuş, mutedil bir tutum benimsemiştir. Ettafeyyiş'in sünnî mezhepler ile ittifak ettiği meseleler doğrultusunda İbâzıyye mezhebinin ahkâm konusunda Hâricîlerden ziyade sünnî mezhepler ile olan benzerliğinin daha fazla olduğu tespit edilmiştir.
Keywords: Coran -- Commentaires -- 19e siècle

Enquête Ethnobotanique des plantes médicinales utilisée pour le traitement des problèmes rénaux dans la wilaya de Ghardaïa - Baghbagha, Amel (Université de Ghardaia, 2025)
Keywords: Botanique -- Mzab; Médecine -- Mzab

Les mouvements contestataires au sein de l’ibadisme maghrébin à l’époque médiévale (IIe-VIIe / VIIIe-XIIIe) - Bahmani, Salah (Ecole Pratique des Hautes Etudes, 2025)
Entre le IIe/VIIIe et le VIIe/XIIIe siècle, l’ibadisme maghrébin a connu une série de dissidences internes qui ont marqué son évolution politique, juridique et théologique. Cette thèse se propose d’en retracer l’histoire, tout en défendant l’idée que ces mouvements contestataires ne doivent pas être perçus comme de simples incidents marginaux, mais comme des acteurs à part entière du développement doctrinal de l’ibadisme. À travers l’analyse croisée de sources historiques, juridiques et théologiques, nous montrons que les mouvements contestataires ibadites ne furent pas de simples ruptures conjoncturelles, mais des facteurs structurants dans l’évolution de la pensée du groupe. Ces mouvements, parfois éphémères, ont contribué à redéfinir les équilibres entre pouvoir central et autonomie locale, tout en nourrissant des débats doctrinaux majeurs sur l’imamat, la nature du pouvoir, les conditions de sa légitimation, la responsabilité religieuse, ou encore la validité de certaines pratiques rituelles. Ces dissidences ont ainsi joué un rôle dans la formalisation progressive des normes de l’orthodoxie ibadite. Nous postulons que c’est dans la confrontation avec ces courants dissidents que s’est élaborée, progressivement, une orthodoxie ibadite maghrébine construite par l’exclusion, la marginalisation ou l’assimilation partielle des mouvements concurrents. En ce sens, l’étude des conflits internes offre un accès privilégié aux mécanismes de construction doctrinale et à la fabrique de la mémoire communautaire, éclairant la manière dont une tradition religieuse gère sa propre pluralité pour assurer sa cohésion, préserver sa légitimité et transmettre une mémoire collective structurante, garante de son identité sur le long terme.
Keywords: Ibadisme -- Afrique du Nord; Nukkarisme

البعثات العلمية الميزابية إلى تونس (1691-1881) - ضاوي, نور الهدى (جامعة محمد خيضر, 2025)
Keywords: Emigration -- Mzab -- Tunisie

Seals in the Early Iron Age "1300-300 B.C.E." in the Oman Peninsula: Case Studies from Salut in Bahla and Dibba Al-Baiya’ah in Musandam - Alawi, Reem Mohammed Said al- (Sultan Qaboos University, 2025)
Keywords: Archéologie -- Oman

A preliminary assessment of the potential production activity in Arab period Malta (870-1091/1127 AD) - Micallef, Joshua (Rheinische Friedrich-Wilhelms-Universität Bonn, 2025)
The scope of this study is to provide a preliminary analysis of the potential production activity undertaken in Malta during the Arab period. The study aims to collate and analyse the available evidence for the period, such as archaeological, historical, geological, and environmental data, and provide an informed picture of the production activity, including such topics as land-use potential and strategies, economic production, and possible practices of adaptive risk management. The research emphasises the importance of the landscape and environmental context, with Geographic Information System (GIS) tools employed to map and analyse site-level agricultural potential, hydrological resources, and proximity to productive landscapes. Thanks to pottery finds, sites of activity or occupation were identified. These sites include one urban site, two coastal sites, and three rural sites. All sites have access to agriculturally suitable land, but to varying degrees, with the sites in the west and north of the island having the greatest potential within a 1 km radius. All sites are also in the vicinity of hydrological resources. While small-scale irrigation or rainwater harvesting methods may have been used, the absence of large-scale irrigation infrastructure suggests limited necessity for such costly undertakings, possibly due to the population size and varied microenvironments that allowed for diverse food production throughout the year. Animal husbandry and apiculture were also practicable, especially since the island has substantial waste ground, such as karstic land with limited agricultural potential but ideal for grazing. Thus, the production of varied foodstuffs would likely not have impinged on each other. Pottery production has also been identified. The nature of the sedimentary geology of the island, which results in calcium carbonate-rich clay, has been identified as one of the issues that would have impacted pottery production. So too is the availability of fuel, seeing the generally degraded steppe environment and limited tree cover present during the period. What also emerges from the study is a picture of an island that is not an uninhabited or forgotten backwater. However, it seems that the Aghlabid overlordship of the island in the ninth century could have resulted in general neglect of the island’s potential, which is reversed starting in the early tenth century under the Fatimids. The study also highlights the clear and evident need for additional research, especially of a scientific nature, and publication of the archaeology of Arab period Malta. Such efforts would be a boon to our understanding of this often-overlooked period of the history of the Maltese Islands and help further elucidate agricultural practices, trade dynamics, and adaptive strategies during the Arab period in Malta.
Keywords: Archéologie -- Malte

علاقات السياسية والثقافية بين المشرق والمغرب في عهد الدولة الرستمية 160-297هـ/777-909م - ترايعية, ليندة; منهان, شيرين (جامعة 08 ماي 1945, 2025)
Keywords: Dynastie rustumide; Vie politique -- Afrique du Nord

دور المؤسسات الخيرية في التنمية الاجتماعية بجمهورية مالي (جمعية الاستقامة نموذجا) = Le rôle des institutions caritatives dans le développement social au Mali. (L’association de la bienfaisance et la droiture en islam au Mali. -A.B.D.I.M- comme modèle) - كان, شيخ أمادو (جامعة أفريقيا الفرنسية العربية الأهلية, 2024)
Keywords: Ibadisme -- Mali

Évaluation de la qualité des eaux albiennes de la région de l'oued M'zab à l'aide de l'indice de qualité des eaux - Tahar, Ikram; Sendjal, Chourouk (Université de Ghardaia, 2025)
Les ressources d’eau d’oued M’Zab sont des eaux souterraines non renouvelables à cause du climat sec de la région. Une compagnie d'échantillons de 18 puits de différentes points de l’amont vers l’aval du la vallée d’oued M’Zab. Les analyses physico-chimiques ont été faites en laboratoire (ADE), et l’Indice de Qualité de l’Eau (IQE) a été calculé à l’aide d’un programme Excel basé sur les équations mathématiques internationales et des normes algériennes. Les résultats montrent que l’eau de la région est globalement de bonne qualité avec un IQE moyen de 48,06, 62 % des puits en eaux de bonne qualité et 38 % en eau de mauvaise qualité. Les bonnes qualités d’eau se trouvent principalement à Daïa et Ghardaïa, tandis que les mauvaises qualités sont observées à l’aval, surtout à El’ Atteuf , zone agricole où se trouve les eaux stagnantes et l’activité agricole. Tous les échantillons dépassent les normes algériennes pour les sulfates et la dureté tandis que les éléments de pollution sont négligeables à cause de la forte minéralisation.
Keywords: Irrigation -- Mzab; Puits -- Mzab

El-i̇bazi̇ye’de (doğu'da umman'dan bati'da kuzey afri̇ka'ya kadar) hi̇cri̇ 1.Yyüzyilin ortasindan 3.Yyüzyila kadar si̇yasi̇ ve fi̇kri̇ hareketler - Yaseen, Sufian Khairadeen Yaseen (Harran Üniversitesi, 2024)
Keywords: Ibadisme -- Afrique du Nord; Ibadisme -- Oman

Credit, Debt and the Omani Community in Zanzibar in the late nineteenth century - Harthi, Amira Sulaiman Ali al- (Durham University, 2025)
Despite the expanded literature of Omani history in Zanzibar in the nineteenth century, few studies have been focused on the patterns of credit and debt of them. This thesis examines the nature of Omani community in living with others and how people made decisions about what sort of business to do, whom to borrow from or lend to, and whom to do business with. Using a sample of one thousand transactions to illustrate the idea of credit and debt patterns between Omanis and other groups that lived in Zanzibar. This study offers a problematic argument of nisba and raising a question of who was giving nisbas to these people. This study presents the active roles of women as moneylenders and borrowers, and how the social rank is reflected in dress and clothing styles. Through an analysis of these transactions, this thesis explores the different approaches of cosmopolitan Zanzibar and how these various meanings can be seen through the credit and debt process of a diverse people living in Zanzibar. Also, we conclude that there are two distinct ways of understanding cosmopolitanism in Zanzibar through transactions. Firstly, Zanzibar society in the nineteenth century involved people from various ethnicities and backgrounds, which might be seen as a kind of cosmopolitanism involving ‘modernity’ and ‘openness’ to different cultures. Secondly, the society that included multiethnic people, could be seen as divided and categorised by their status and ethnicity
Keywords: Commerce -- Zanzibar -- 19e siècle

Spaces of Resistance: Reflections on Algerian Domesticity - Laksari, Naïla (Carleton University, 2025)
Keywords: Architecture -- Mzab

تطور الفكر الأصولي عند الإباضية: دراسة وصفية - السعيدى, فيصل بن على بن سليمان (جامعة العلوم الإسلامية العالمية, 2025)
Keywords: Foi -- thèmes et motifs

ديوان "غرداية" لعثمان لوصيف دراسة في جماليات المكان - بلعور, سمية (جامعة غرداية, 2025)
شغل المكان في الشعر الجزائري المعاصر حيزا واسعا من الاهتمام، فكان المحرك الأساسي والعنصر الملهم للشعراء، وتهدف هذه الدراسة إلى استقصاء تمثلات المدينة في الشعر الجزائري من خلال نموذج ديوان غرداية لعثمان لوصيف فأصبح المكان في الشعر الحديث مكونا بنيويا يُسهم في تشكيل المعنى، ولم يعد مجرد خلفية جامدة للأحداث أو الانفعالات، بل تحول إلى عنصر تعبيري يعكس مواقف الشاعر. جاء اختيار مدينة غرداية نظرا لما تتميز به من رمزية خاصة ضمن السياق الجزائري، إذْ تُشكِّل ملتقى للهوية والتراث وفضاء مشبعا بالروحانية والتقاليد، ما جعلها مادة خصبة للتخيل الشعري. وكشفت الدراسة عن قدرة الشاعر عثمان لوصيف على توظيف غرداية كشخصية شعرية فاعلة، تحمل دلالات الأنثى، والصفاء، والانتماء، وكيف يتحول المكان في بعض التجارب الشعرية إلى مرآة للذات، ومجال للتأمل، خاصة حين يرتبط بالبعد الصوفي. وهذا ما منح المدينة بعدا جماليا. Occupying space in contemporary Algerian poetry occupies a prominent situation and produces great interest. It is the main and short track for the poet's, awarness, and from this entrance cultural movement in Algerian poetry are inspected through a selected illustrative, namely the poet "Othman Loucif" in his troupe “Ghardaia place contributes to the formation of meaning”. The study does not stop at presenting fastened and remoted data but shifts on the way to change the place into an Suggestive poetic section With Denotation back. The poet indicates his identity through it representing memory, the self and spritual devotion, with all the linked feelings of isolation and yearing. The study revealed the poet’s capacity to employ place in a poetic imaginative way, surround many implication like forgetting , dropping and eviction. Place transforms for Some young poets into a space for reflection and examine the present. Especially when it is linked to phonetic dimension, it presents the poem additional richness.
Keywords: Poésie -- Mzab

Inventaire, Evaluation et étude de la répartition du Pistacia atlantica Desf dans les communes de Beriane et Guerrara (wilaya de Ghardaia). - Lassakeur, Mouna; Ben Alia, Zohra (Université de Ghardaia, 2025)
Keywords: Agriculture -- Mzab

Impact de l’irrigation sur la distribution spatiale du carbone organique dans les sols de la région de Ghardaïa (cas de Daya Ben Dahoua) - Dahou, Rahma; Ouled Eltayeb, Ibtessem (Université de Ghardaia, 2025)
Keywords: Irrigation -- Mzab

مدينة زوارة دراسة في جغرافية المدن - بيري, الهيثم اسماعيل (جامعة طرابلس, 2024)
Keywords: Géographie -- Zouara

حرف "التيفيناغ" ودوره في إثراء الموروث الزخرفي الليبي في منطقتي جبل نفوسة وزوارة - السباعي, غالية علي (جامعة طرابلس, 2024)
تضمنت هذه الدراسة حرف "التيفيناغ" ودوره في إثراء الموروث الزخرفي الليبي في منطقتي جبل نفوسة وزوارة، وقد اشتملت على أربعة فصول وملحقين. تناول الفصل الأول الإطار المنهجي للدراسة الذي شمل مشكلة البحث وإجراءاته، متمثلاً في خلفية البحث، ومشكلته، والهدف منه، وأهميته وفروضه وحدود الدراسة ومنهجيتها، وأخيرا المصطلحات التي تتصل بموضوع الدراسة، والفصل الثاني كان عبارة عن سرد تاريخي للخلفية التاريخية والحضارية عن سكان ليبيا القديمة خلال العصور القديمة والوسطي، وقد انقسم هذا الفصل إلى أربعة محاور، تم فيها تناول أهم الهجرات التاريخية التي مرت على ليبيا القديمة، وكذلك اسم ليبيا وارتباطها بالشمال الأفريقي عبر العصور، وتناول أيضاً ليبيا والليبيين القدماء من خلال المصادر المصرية والإغريقية والرومانية، والبيزنطية، وبعض القبائل الليبية خلال العصور الوسطى(جبل نفوسة –وزوارة نموذجا). أما الفصل الثالث فكان بعنوان، الحرف الليبي القديم "التيفيناغ" ومراحل تطوره واستلهام الحرف في أعمال الفنون الشعبية التشكيلية، وقد تضمن هذا الفصل خمسة محاور، تم فيها تناول اللغة الليبية القديمة "التيفيناغ"(نشأتها- تطورها)، وظهور حرف "التيفيناغ" على المسطحات الصخرية مع رسومات عصور ما قبل التاريخ، وكذلك أوجه التشابه بين شكل حرف "التيفيناغ" وشكل بعض حروف العالم القديم وكتاباته. هذا إلى جانب استلهام حرف "التيفيناغ" شكلاً جمالياً ورمزاً، وحرف "التيفيناغ" واستخدامه في الصناعات اليدوية(النسيجية والمعدنية). بينما تضمن الفصل الرابع والأخير الجانب التطبيقي للدراسة، فكان بعنوان حرف "التيفيناغ" وإمكانية استخدامه في عمل تصاميم حديثة ومبتكرة، حيث انقسم هذا الفصل إلى ثلاثة محاور، تم فيها وصف لحرف "التيفيناغ" وتحليله، بالإضافة إلى عمل جداول ذات ترقيم تصاعدي توضح آلية تطبيق الحرف المراد نقشه، مرفق بشكل توضيحي للحروف وتكرار بعضها لإنتاج الزخارف باستخدام الحاسب الآلي، وأخيراً عمل تصاميم مبتكرة باستخدام الحاسب الآلي وإدراج بعض النماذج المستحدثة من تصميم الباحثة، تجمع فيها ما بين حرف "التيفيناغ" والزخارف الموجودة في المنطقة. من أهم أهداف هذه الدراسة هو الكشف عن القيم الفنية والجمالية لحرف "التيفيناغ" ومقارنتها ببعض الأشكال الزخرفية في منطقة الدراسة(جبل نفوسة وزوارة)، كما سعت هذه الدراسة إلى تطوير حرف "التيفيناغ" وتوظيفه في عمل تصاميم مبتكرة تحمل الهوية الليبية البحتة بشكل أكثر حداثة وشمولية، بحيث يتلخص فيها الموروث الثقافي الليبي والقيم الليبية الأصيلة. بينما نجد أن فروض هذه الدراسة كانت تتمحور حول وجود علاقة بين بعض حروف "التيفيناغ" وبعض الزخارف الشعبية الموجودة في منطقة جبل نفوسة وزوارة، هذا بالإضافة إلى فرضية وجود تأثيرات للمعتقدات الدينية، والفلسفية، والتاريخية المختلفة التي مرت بالمنطقة عبر العصور على أشكال بعض أنواع الزخارف، هذا إلى جانب إمكانية عمل تصاميم مبتكرة يتم فيها الجمع بين حروف "التيفيناغ" وبعض أنواع الزخارف لإثراء الموروث الثقافي الليبي. اتبعت الباحثة في هذه الدراسة المنهج التاريخي الوصفي، وذلك ضمن إطارين معرفي وتطبيقي، هذا بالإضافة إلى إجراء المقابلات الشخصية لعدد من كبار السن من الجنسين، لغرض الحصول على المعلومات المتعلقة بأشكال الوشم، والوسم، والمسميات الخاصة بهما، المتعارف عليها في منطقة الدراسة وقد تم توثيق هذه الأسماء في الجداول من رقم(8-16) التي كانت بعنوان شكل الوسم واسم العائلة واسم المصدر. ومن أهم نتائج هذه الدراسة ما يلي:_ 1- أغلب أنواع الزخارف والنقوش الموجودة في منطقة الدراسة(جبل نفوسة وزوارة) سواء أكانت على النسيج أم الحلي المعدنية أم الوشم أم الوسم في نظر الباحثة، هي عبارة عن تكرار لبعض أنواع حروف "التيفيناغ". 2- تمكنت الباحثة من تطوير استخدام حرف "التيفيناغ" بواسطة الحاسب الآلي، وتوظيفه في عمل تصاميم مبتكرة تتماشي مع ظروف الحياه في الوقت الحالي. 3- وجود تأثيرات للمعتقدات الدينية المختلفة التي مرت بالمنطقة متمثلة في الآتي: أ- هناك تأثير للحضارة الليبية القديمة، متمثلة في شكل حرف التاء(+)، (القاطع المقطوع) استخدم هذا العنصر في الوسم، والوشم وفي بعض الحلي المعدنية. ب- هناك تأثير لمعتقد الديانة الوثنية، متمثلاً في شكل اليد المفرودة(الخميسة) التي تستخدم لمنع الحسد والروح الشريرة، وأيضاً شكل يمثل الإلهة تانيث الفينيقية على بعض نقوش الحلي المعدنية. ج- هناك تأثير للفنون القديمة، متمثلاً في شكل النجمة السداسية. د- هناك تأثير للدين الإسلامي في المنطقة، متمثلاً في شكل الهلال، والنجمة الخماسية على بعض أنواع الحلي المعدنية مثل حلي "تاقتوفت" (المقطوف). ه- وجود تأثيرات فنية كثيرة متوارثة عبر العصور التاريخية، متمثلة في شكل نقش الوشم، وبعض نقوش الحلي المعدنية، بالإضافة إلى زخارف النسيج سواء أكان المستخدم للباس، مثل الجرد بأنواعه المختلفة، أم النسيج المستخدم للاستعمالات الأخرى، مثل المنديل، والوسادة والكليم، متمثلة في تكرار لشكل المثلث (الزقزاق) و شكل الخطوط بأنواعها وغيرها. ثانياً / التوصيات في ضوء ما أسفرت عنه نتائج البحث فإن الباحثة توصي بالآتي. 1- دراسة ظاهرة الوشم وارتباطها بالمعتقد الديني والثقافي والحضاري في المجتمع الليبي. 2- دراسة ظاهرة الوسم وعلاقتها بالموروث الثقافي والحضاري في ليبيا. 3- دراسة حرف "التيفيناغ" من زاوية شكله ومراحل تطوره في منطقة المغرب الكبير. 4- دراسة شكل نقوش الحلي المعدنية وتصنيفها عند المرأة الليبية وعلاقتها بحروف "التيفيناغ". 5- دراسة النقوش والرموز الموجودة على جدران وأسقف العمارة السكنية وغيرها في منطقة جبل نفوسة وعلاقتها بحروف "التيفيناغ".
Keywords: Arts -- Djebel Nefousa

Exploration des potentiels anti-radicaux des extraits de quelques espèces extrêmophiles au Sahara Algérien - Djekaoua, Meriem; Chenini, Ahlam (Université de Ghardaia, 2025)
Keywords: Botanique -- Mzab

Le chant traditionnel de l'ile de Djerba (approche anthropologique) - Tlili, Wissem (Institut supérieur des cadres de l'enfance, 2024)
Keywords: Moeurs et coutumes -- Djerba; Musique -- Djerba

The Role of a Small State in a Regional Security System: The Case of Oman - Shibli, Miysaa Khamis Rashid al- (The University of Hamburg, 2025)
This thesis explains the prevailing paradigm of the role of small states in regional security systems, and fundamentally examines the case of Oman as a small country that has managed to play a significant role in the Middle Eastern regional security system, contrary to conventional political science expectations of such states’ behavior as per the neoclassical realism theory (NRT) paradigm. This thesis explains Oman’s different and independent regional positions, notably: (1) supporting the Camp David Peace Accords (1978) and not joining the Arab League and Gulf boycott of Egypt after Sadat’s rapprochement with Israel; (2) developing and maintaining diplomatic ties with Iran after the 1979 Revolution, when it was seen as an imminent threat to Gulf regimes, and during the Iran-Iraq War (1980-1988); (3) meditating between Iran and the US in the P5+1’s Joint Comprehensive Plan of Action (2015) (i.e., the “Iran Nuclear Deal”); and (4) preserving regional security in the context of the ongoing Yemen conflict. This thesis examines these cases in light of hitherto unutilized sources (such as newspapers, official documents, gray literature, archives, memoirs, local books, reports, memos) and interviews with key experts involved in Oman’s foreign policy and related events. This thesis thus demonstrates that Oman as a small state was able to tangibly and effectively influence the regional security system through a balanced foreign policy and establishing spaces that support dialogue and diplomacy to address regional tension and conflicts and maintain relative neutrality in most regional and international conflicts.
Keywords: Politique étrangère -- Oman -- 1970-2020

Continuity and change in traditional domestic architecture: The case of a community-led housing project in Ksar Tafilet, M'zab Valley - Messabih, Hadjer (Cardiff University, 2025)
This thesis explores the sociocultural continuity and residents’ adaptations to 21st-century conditions within a community-led housing project undertaken by the conservative Mozabite community in the M’zab Valley, Algeria. Using Ksar Tafilelt as a case study, which is a community-led housing project, the research examines the established co-production process to develop a new housing settlement that addresses the needs of the contemporary Mozabite community. It also identifies key lessons in sustainability that can be drawn from this unique and fully realised community-led housing project by examining the relationship between social behaviour and the built environment. The study methodology relies on a combination of questionnaires, interviews, a research diary, and records of physical traces. A sample of 70 residents was interviewed, and various indicators were employed to examine the different types of adaptive transformation changes needed in residents’ homes and neighbourhoods to better meet their contemporary needs. The use, organisation, and occupation of space at both the domestic scale of the house and the urban scale of the neighbourhood have been analysed. Residents’ evaluations and satisfaction with their dwellings and neighbourhoods have also been investigated and assessed in relation to various physical and non-physical features of their housing environments, with a focus on sociocultural factors. The findings of this research indicate that the sociocultural values transmitted from the indigenous Ibadi community remain deeply entrenched in the contemporary Mozabite community, significantly expressed architecturally in Ksar Tafilelt. Thus, these findings suggest that the sociocultural needs of residents must be regarded as equally important as environmental and economic factors. Furthermore, the research iii outcomes have yielded several lessons and principles that can be derived from this settlement, which may inform future housing provision and design practices in Algeria and beyond, particularly in regions with similar geo-cultural characteristics. These lessons can be summarised as highlighting the importance of involving the local community in the creation of urban dwellings to enhance living conditions, as long as the design aligns with their sociocultural and religious beliefs. Additionally, it is crucial to consider the role of sociocultural factors in fostering a more socially and culturally sustainable built environment.
Keywords: Urbanisme -- Mzab

Variation spatio-temporelle et statistique de la qualité des eaux souterraines de la ville de Ghardaïa - Ben Sedira, Abdelkader (Université de Ghardaia, 2025)
Keywords: Puits -- Mzab

Coutumes et traditions de la Kabylie et Oued Mzab, une étude anthropologique comparative - Messouaf, Youcef (Université de Batna 1, 2025)
Keywords: Droit coutumier -- Mzab; Moeurs et coutumes -- Kabylie; Moeurs et coutumes -- Mzab

Pour une exploitation linguistique des anciens manuscrits berbères et arabo-berbères en graphie arabe. Essai de valorisation numérique - Meziani, Noumidya (Université El-Hadj Lakhdar, 2025)
Keywords: Linguistique

العلماء العميان في بلاد المغرب الإسلامي خلال القرون 5-9هـ/ 15-11مـ - دراسة نماذج - - خياط, محمد (جامعة غرداية, 2024)
لقد تطرق هذا البحث إلى نماذج من حياة العلماء العميان وأبرز آثارهم العلمية ببلاد الغرب الإسلامي خلال القرون 5_9ه/ 11_15م ومن هؤلاء نذكر: أبو الحسن الحصري الفهري الضرير ت 488ه: الذي نشأ بمدينة القيروان وقد فقد بصره مبكرا لكن ذلك لم يمنعه من حفظ القرآن وتلقي علوم الأدب والفقه والتف سير وعلم القراءات، رحل إلى مدينة سبتة حيث اشتغل بالتدريس، ثم اتجه نحو الأندلس بدعوة من المعتمد بن عباد حيث تزوج هناك وطاف بين أمرائها إلى أن غادرها إلى مدينة طنجة أين توفي بها، ألف العديد من القصائد مثل: "ديوان اقتراح القريح واجتراح الجريح" ومنظومة في القراءات. أبو محمد ماكسن بن الخير ت 491ه: من عائلة إباضية ولد بمدينة القيروان، فقد بصره في السنة السابعة من عمره، حفظ القرآن بكتابها، ثم انتقل إلى مدرسة أبي محمد ويسلان بجربة أين اعتنى به شيخه وحظي برفقة حسنة ساعدته على النبوغ، ثم رحل إلى مدينة وارجلان ومنها إلى منطقة وادي ريغ التي برز فيها نشاطه في إحياء العلم والدعوة إلى الإصلاح، وقد نقلت الكتب الفقهية الإباضية الكثير من أقواله وفتاويه. الأعمى التطيلي ت 525ه: نشأ بمدينة إشبيلية وتلقى العلوم في مدارسها، كما فقد بصره في سن مبكرة، رافق كبار الوشاحين حتى برع وتبوأ فيه مكانة راقية في عصره، كما ألف في الشعر بمختلف أغراضه كالمدح والرثاء. ابن مرزوق العجيسي الكفيف ت 901ه: نشأ في كنف عائلة مشهورة بالعلم بمدينة تلمسان، اعتنى به والده في التعلم، كان من كبار الأئمة والخطباء وعلماء الحديث، وله أثر بالغ في الحياة الثقافية بتلمسان، ويكفي أنه قد تخرج على يديه صاحب كتاب المعيار أبو العباس الونشريسي، ومما ألف: "شرح متختصر الحاوي للفتاوي". This research deals with examples of some blind scholars and their most prominent scientific legacy in the Islamic West between the 5th-9th centuries AH/11th-15th centuries AD: Abu al-Hasan al-Hasri al-Fahri al-Dharir (d. 488 AH): He grew up in Kairouan, Tunisia. He lost his sight early, but this did not prevent him from memorising the Qur'an and mastering several Qur’anic disciplines: literature, jurisprudence, Quran commentary, and Quran recitation. He travelled to Ceuta, where he worked as a teacher, then went to Andalusia at the invitation of al-Mu'adhad ibn Abbad, where he got married and visited its princes until he left it to the city of Tangier, where he died, he wrote many poems such as: "Diwan al-Qurayh and Ijtirah al-Jurayh" and a poem collection in Quran recitation. Abu Muhammad Maksin ibn al-Khair (d. 491 AH): He was born in the city of Kairouan, he lost his sight at the age of seven, memorised the Qur'an, then he moved to the school of Abu Muhammad Weslan in Djerba, where his sheikh took care of him and kept him good company that helped him to excel, then he left for the city of Warjalan, Algeria, and then to the Wadi Rig region, where his scientific and reformist activity emerged. Additionally, many of his statements and fatwas were quoted in Ibadi fiqh books. Al-A’ma al-Tutaili (d. 525 AH): He grew up in the city of Seville and received knowledge in its schools. He lost his sight at an early age. He accompanied the great poets until he excelled in poetry and obtained a high position in it, and wrote poems in various purposes such as praise and lamentation.

Territoire et patrimonialisation en Tunisie: enjeux de pouvoir ? - Bielawski, Mathilde (Université de Lyon, 2022)
Le présent travail de recherche se veut être une étude critique du « patrimoine culturel tunisien » en contexte « post-printemps arabe ». L’objectif est d’enrichir les connaissances sur le domaine de la conservation et de la gestion du patrimoine en Tunisie. C’est afin de mieux comprendre le contexte actuel dans ce domaine que la réflexion s’oriente autour de l’articulation des pouvoirs nationaux (institutions étatiques) et d’une nouvelle « société civile postrévolutionnaire » — notamment à travers les associations dites « de sauvegarde du patrimoine » — comme nouveaux enjeux des pays en transitions et mutations politiques et économiques. Cette étude anthropologique s’est déroulée de 2014 à 2020. Elle s’est concentrée sur le suivi du processus d’inscription de l’île de Djerba en Tunisie sur la Liste du patrimoine mondial de l’Unesco, afin d’amener à comprendre les enjeux de gouvernance territoriale en contexte « postrévolutionnaire ». Les enquêtes réalisées entre Tunis la capitale et l’île de Djerba au sud du pays, se sont intéressée aux relations entretenues entre les institutions d’État responsables du dossier et l’Association de Sauvegarde de l’Île de Djerba (Assidje), partenaire de l’État tunisien sur ce projet. Cela a permis d’étudier un « patrimoine culturel » en train de se « fabriquer » et d’en saisir les enjeux de gouvernance territoriale qui y sont liés. The research area of this work is the critical heritage study of “Tunisian cultural heritage” in the “post-Arab Spring” context. The objective is to contribute to the knowledge of the field of conservation and management of cultural heritage in Tunisia. To better understand the current context in this field, the study focuses on the articulation of national powers (state institutions) and a new “post-revolutionary civil society” - in particular through the so-called “heritage preservation associations” - as new challenges for countries undergoing political and economic transitions and changes. This anthropology study took place from 2014 to 2020. It focused on the monitoring of the process of inscription of Djerba island in Tunisia on the Unesco World Heritage List, to understand the issues of territorial governance in a “post-revolutionary” context. The investigations carried out between the capital Tunis and Djerba island in the south of the country, focused on the relations maintained between the State institutions in charge of the case and the Association for the Safeguarding of Djerba Island (Assidje), a partner of the Tunisian State on this project. This allowed us to analyse a “cultural heritage” in the process of being “made” and to understand the issues of territorial governance that are linked to it. يضع هذا البحث في صلب اهتمامه قراءة نقدية للتراث الثقافي التونسي ما بعد الربيع العربي. يهدف هذا البحث ايضا الى اغناء مجال المعرفة حول المحافظة على التراث الثقافي في تونس وتدبيره. ولهذا الغرض، ارتأينا دراسة مؤسسات الدولة و جمعيات المجتمع المدني التي تعنى بالمحافظة على التراث كمعيار لدولة في وضعية انتقالية ومن اجل انجاح هاته الدراسة، تم الاعتماد على منهجية انتروبولوجية و دراسة ميدانية ما بين 2014 و 2020 هدفها تتبع عملية تسجيل جزيرة جربة في تونس في قائمة التراث العالمي لليونسكو، من أجل فهم تحديات الحكم الإقليمي في سياق "ما بعد الثورة". اهتمت الدراسات الاستقصائية المنجزة بين العاصمة تونس وجزيرة جربة جنوب البلاد بدراسة العلاقة بين مؤسسات الدولة الساهرة على الملف وجمعية المحافظة على جزيرة جربة، شريك الدولة التونسية في هذا الملف. هذا يسمح لنا بدراسة التراث الثقافي في عملية "صنعه" وفهم التحديات ذات الصلة بالحكامة المحلية
Keywords: Monuments -- conservation -- Djerba

نماذج من منازل جزيرة جربة: دراسة تاريخية و اثرية - بن عثمان, نسرين (كلية العلوم الأنسانية والإجتماعية, 2024)
Keywords: Architecture -- Djerba

منهج الخوارج في تفسير آيات الاعتقاد تفسير هميان الزاد إلى دار المعاد أنموذجًا - محمود, مصطفى محمد (Bingöl University, 2025)
الملخ ص: خلاصة البحث تدور حول تعريف الخوارج وصفاتهم وفرقهم وآرائهم وعقيدتهم وأسباب خروجهم، وتسليط الضوء على الإباضية الأولى والمعاصرين، والفَرق بينهما، وبيان منهج الخوارج في التفسير وتأويلهم لآيات الَّعتقاد، وعرض ذلك على ضوابط التفسير، مع مقارنته بنقل بعض أقوال العلماء والمفسرين من غير الخوارج؛ وكان ذلك من خلال الوقوف على أشهر المسائل الَّعتقادية والآيات التي ذكرَتها. وكان تفسير "هميان الزاد إلى دار المعاد" أنموذجاً للنظر في منهج مصنفه ومنهج مَن وافقه أو خالفه في تأويل تلك الآيات، وإظهار ما وقع فيه من الصواب الموافق، أو الخطأ المخالف؛ وكان من لوازم ذلك التعريف بهذا المصنَّف وبمن صنَّفه. وبيان تأويل المتشابه، ومكانة السنة من القرآن، والفِرق التي تعتمد على القرآن والسنة أو تفرِّق بينهما. ودورُ بعض مباحث علوم القرآن في تفسير وتأويل القرآن وآيات الَّعتقاد، وتعريف البدعة والهوى وأهل الأهواء، وسبب الَّختلاف في التفسير. وتناول البحث أهمَّ المسائل الإيمانية؛ كمسألة التوحيد والإيمان وثبوته وزواله، وزيادته ونقصانه، والكفر والشرك والنفاق، والذنوب الصغائر والكبائر، والوعد والوعيد والخلود في النار، والتوبة والمغفرة، والأمر بالمعروف والنهي عن المنكر، وصفات الله تعالى ورؤيته، وأ ركان الإيمان، والهداية والضلال، وخلق أفعال العباد، وما شابه ذلك. ثم دراسة وبيان قيمة منهج الخوارج في تفسير آيات الَّعتقاد، مقترنا بأقوال بعض المفسرين من أهل السنَّة. وخُتم البحث بخاتمة تضمنَّت أهم النتائج والتوصيات المتعلقة بهذه الدراسة
Keywords: Coran -- Commentaires -- 19e siècle

الأقوال الفقهية في سِيَر إباضية المغرب إلى نهاية القرن العاشر الهجري جمعا، وترتيبا، ودراسة - أمعيز الحاج أحمد, حسن (جامعة الزيتونة, 2025)
Keywords: Fiqh -- Ibadisme

النظرة المقاصدية في اختـــيار الإمام الحاكم وأهل الحل والعقد عند العُمانيين وأثرها في تحقيق القيم السياسية" - السعدي, طالب بن علي بن سالم (كلية العلوم الشرعية, 2024)

الشيخ الدكتور عاشور بن يوسف كسكاس وإنتاجه العلمي ومسيرته الدعوية - السيابي, سلام بن سعيد بن سلام (كلية العلوم الشرعية, 2024)
Keywords: Biographies -- Djerba -- 20e siècle

From Jadu to Cairo: Ibadi Women Refashioning Identity and Gender in the Early to Mid-20th Century - Khamoosh, Sahar (Al Akhawayn University, 2023)

دلالة النهي على فساد المنهي عنه عند الأصوليين وتطبيقاتها الفقهية عند الإمام السالمي (ت : 1332هــ) - الحبسي, مروان بن محمد بن سرحان (كلية العلوم الشرعية, 2022)

المرأة العمانية في كتابات المستشرقين (دراسة تحليلية) - الرشيدية, صفية بنت حمد بن سعيد (كلية العلوم الشرعية, 2024)

الأقوال الأصولية للبدر الشماخي في كتاب شرح مختصر العدل والإنصاف جمع و مقارنة - النظيري, صالح بن حمود بن أحمد (كلية العلوم الشرعية, 2024)

الشخصية المتوازنة في السنة النبوية من خلال مسند الإمام الربيع بين حبيب (ت: 175هـ) - الغماري, سيف بن علي بن سعيد (كلية العلوم الشرعية, 2022)

القواعد والضوابط الفقهية وتطبيقاتها عند الإباضية من خلال مدونة أبي غانم الخراساني ق (2هـ) - المقيمية, راية بنت حمود بن سبيت (كلية العلوم الشرعية, 2022)
Keywords: Fiqh -- Libye -- 8e siècle

رسالة في رد المطلقة ثلاثا تأليف الشيخ جاعد بن خميس بن مبارك الخروصي (ت 1237 هـ) دراسة وتحقيق - الخليلي, عمر بن أحمد (كلية العلوم الشرعية, 2025)

نخبة المتين من أصول تبغورين لعمرو بن رمضان التلاتي الجربي (ت: 1187 هـ) دراسة وتحقيقا - سليمان, حنان بنت عبد العزيز (كلية العلوم الشرعية, 2022)

الإصلاح المجتمعي وأثره على الدعوة من خلال جواهر التفسير لسماحة الشيخ أحمد الخليلي - الرواحي, إسحاق بن عبد الله بن خميس (كلية العلوم الشرعية, 2022)

المقاييس في الأثر الإباضي المشرقي و المسائل الفقهية المتعلقة بها (الأطوال و المكاييل و الموازين) - الراشدي, الأزهر بن يوسف بن هلال (كلية العلوم الشرعية, 2023)

الشيخ ناصر بن جاعد الخروصي (ت: 1262هـ) و منهجه في شرح تائيتي ابن الفارض (632 هـ) - الصقري, يوسف بن محمد (كلية العلوم الشرعية, 2021)

القواعد الفقهية المتعلقة بالقضاء و تطبيقاتها في الفقه الإباضي و القضاء العماني - البراشدي, محفوظة بنت علي (كلية العلوم الشرعية, 2023)

اختيارات الإمام نور الدين السالمي الفقهية في أشهر المسائل الخلافية (باب الطهارة نموذجا) - الراشدي, خالد بن مسلم (كلية العلوم الشرعية, 2021)

ترجيحات الإمام السالمي في مسائل فروع العقيدة الإسلامية (دراسة تحليلية) - الزكواني, سالم بن سعيد (كلية العلوم الشرعية, 2021)

منهج التزكية في المدرسة الإباضية بعمان من خلال مؤلفات العمانيين في القرون الهجرية الستة الأولى - الكندية, شمسا بنت سعود (كلية العلوم الشرعية, 2024)

المسائل الفقهية التي خالف فيها العلامة نور الدين السالمي العلامة سالم بن سعيد الصائغي في باب النكاح (دراسة فقهية مقارنة) - الفارسية, عبلة بنت سالم بن علي (جامعة السلطان قابوس كلية التربية, 2021)

تخريج الفروع على الأصول عند السالمي (1284-1332 هـ) العام والتخصيص أنموذجا - حاجي, عيسى إبراهيم (جامعة السلطان قابوس كلية التربية, 2022)

تفسير الصحابي من خلال كتاب الضياء للعوتبي، جمعا وترتيبا - الصارمية, زهرة بنت حمد بن سعيد (كلية العلوم الشرعية, 2024)

علامات الساعة في التفسير الأباضي - الهطالية, نظيمة بنت صالح (كلية العلوم الشرعية, 2024)

آراء ناصر بن جاعد الخروصي العقدية: القضاء والقدر ــ البعث ــ الإمامة - الشبلية, عبير بنت بن سعيد (كلية العلوم الشرعية, 2024)

الشورى عند الإباضية " تنظيرا و تطبيقا " - البحرية, جواهر بنت عبد الله بن سعيد بن عبد الله (كلية العلوم الشرعية, 2022)
Keywords: Idées politiques -- Ibadisme

القواعد الفقهية الدالة على نفي الاعتبار في الفقه الإباضي دراسة مقارنة - الحوسني, الخطاب بن طارق بن محمد (كلية العلوم الشرعية, 2024)

تحقيق كتاب ضياء الهدى المنجي من الردى للشيخ سالم بن حمود السيابي (في أصول الدين) ( من ص1 إلى ص 32) ( ت: 141 هـ) - السيابي, عيسى بن عبد الله بن سالم (كلية العلوم الشرعية, 2024)

منهج الشيخ محمد سعيد كعباش في تفسيره "نفحات الرحمن في رياض القرآن" (سورة البقرة أنموذجا) - العبدلي, إبراهيم بن سيف بن مهنا (كلية العلوم الشرعية, 2024)

الأمر بالمعروف و النهي عن المنكر في الفكر الإباضي و تطبيقاته الدعوية - المشايخية, حنان بنت خميس بن راشد (كلية العلوم الشرعية, 2024)

المدرسة الإباضية الكلامية في عيون الباحثين المعاصرين - الشعيلي, عبد الله بن عيسى بن سليمان (كلية العلوم الشرعية, 2023)
Keywords: Foi -- Ibadisme

رسالة في رد المطلقة ثلاثا تأليف الشيخ جاعد بن خميس بن مبارك الخروصي (ت 1237 هـ) دراسة و تحقيق - الخليلي, عمر بن أحمد بن حمد (كلية العلوم الشرعية, 2025)
Keywords: Fiqh -- mariage

جهود الشيخ عبدالعزيز الثميني (ضياء الدين) العلمية والاصلاحية في مجتمع وادي مزاب مابين 1130-1223ه/ 1718-1808م. - شخار, لقمان (جامعة غرداية, 2024)
يعد موضوع دراسة تراجم وسير الشخصيات التاريخية العلمية الفاعلة في مجتمعاتها العمود الفقري لتقييم وتقويم المسار الحضاري لكل مجتمع، فموضوعي عن شخصية الشيخ عبد العزيز الثميني الإباضي الجزائري من تلك الشخصيات البارزة في واد مزاب الذي عرف بتنظيماته الدينية على رأسها حلقة العزابة وغيرها، بالإضافة الى ترك بصمات واضحة وآثار راسخة في المجال الديني والعلمي ودليل ذلك ما ترك من قيم في عدة مجالات ما يزال اغلبها مخطوطا، وأفواجا من الطلبة المتخرجين على يده من مختلف قصور واد مزاب التي ساهمت في إعادة بعث الروح العلمية والعمل الاجتماعي بها. The study of the biographies and lives of influential historical figures in their societies forms the backbone of evaluating and shaping the civilizational trajectory of every community. My research focuses on Sheikh Abdel Aziz Al-Thaminy, an eminent Ibadi Algerian figure from the M'Zab Valley. He is known for his role in religious organizations, most notably the "Halqat al-Azzaba," among others. In addition to leaving a significant and enduring impact in the religious and scholarly fields, his contributions are evidenced by the values he instilled across various domains, much of which remain in manuscript form. Furthermore, numerous students from the different forts of the M'Zab Valley graduated under his tutelage, contributing to the revival of intellectual and social life in the region.
Keywords: Biographies; Vie intellectuelle -- Mzab

Etude historique de l’autobiographie le sein de ma mère de Slimane Benaïssa - Becis, Rostom (Université de Ghardaia, 2024)
Keywords: Théâtre -- Mzab

رسالة في إعراب كلمة الشهادة للشيخ أبي مهدي عيسى بن إسماعيل المليكي (ت971ه) "دراسة وتحقيق" - عجرود, علي (جامعة غرداية, 2024)
هذا العمل تحقيق ودراسة لكتاب إعراب كلمة الشهادة للشيخ أبي مهدي عيسى بن إسماعيل المليكي وقد سعيت من خلال هذا البحث إلى تحقيق الأهداف التالية: - التعريف بالشارح، وبيان المؤثرات التي ساعدت على إبراز شخصيته العلمية. - تحقيق الكتاب وفق منهج علمي وإخراجه سليما، وذلك بضبط الشواهد، والعمل على توظيف ما من شأنه خدمة النصّ المحقّق. - دراسة الكتاب من حيث ميزته، ومنهج المؤلّف، وأسلوبه. وقد توّج البحث بخاتمة تضمّنت أهمّ النتائج. ثم ختمت هذا العمل بفهارس فنية. وأخيرا أرجو أن أكون قد وفّقت في عرض هذا الكتاب، ووضعه في مكانه المناسب وإضافة لبنة في بنائنا الثقافي وتراثنا الحضاري.
Keywords: Linguistique -- Mzab

الاجتهادات الفقهية للإمام أطفيش (1332هـ) في العبادات من خلال كتاب وفاء الضمانة بأداء الأمانة مقارنة بشرح النيل وشفاء العليل : (دراسة فقهية) - الفارسي, أيمن بن حبيب بن سيف (جامعة السلطان قابوس, 2020)
تهدف هذه الرسالة إلى التعريف بالاجتهادات الفقهية للشيخ أمحمد بن يوسف أطفيش في العبادات من خلال كتابه "وفاء الضمانة بأداء الأمانة" مقارنة بكتاب "شرح النيل وشفاء العليل"، فقد احتوى كتاب "وفاء الضمانة بأداء الأمانة" على أكثر من (300) اجتهاد فقهي للمؤلف، وتسعى هذه الرسالة لإبراز اجتهاداته في فقه العبادات من خلال الإجابة على الأسئلة التالية: 1. ما المقصود بالاجتهادات الفقهية ؟ 2. ماذا رجح الشيخ أطفيش في شرح النيل في المسائل التي وجدت له فيها ترجيحات في وفاء الضمانة في قسم العبادات وهل تختلف اجتهاداته بين الكتابين وما أسباب ذلك؟ 3. ما تأثير حضور النص الشرعي في اجتهادات القطب ؟ 4. ما المنهج الاستدلالي الذي اختاره القطب في كتاب وفاء الضمانة ؟ وللإجابة على هذه الأسئلة قام الباحث باستقراء كتاب وفاء الضمانة، واستخرج منه مواضع الترجيح للمؤلف، ثم قارنها بما يقابلها من كتاب شرح النيل، وخلص إلى مجموعة من النتائج أبرزها: 1. الاجتهاد الفقهي هو : "طلب الفقيه حصول حكم حادثة بشرع، ويبذل في ذلك مجهوده، بحيث لا يمكنه المزيد عليه في الطلب". 2. بلغ عدد المسائل الفقهية التي صرح فيها الشيخ أطفيش برأيه في قسم العبادات (98) مسألة، واتفق اجتهاده بين وفاء الضمانة وشرح النيل في (33) مسألة منها، واختلف في (6) مسائل بين الكتابين، ورجح في (59) مسألة من وفاء الضمانة لم يرجح فيها شيئا في شرح النيل، وانفرد قسم العبادات من وفاء الضمانة بذكر (20) مسألة لم يذكرها في شرح النيل. 3. حضور النص الشرعي في وفاء الضمانة هو أهم سبب من أسباب وفرة الترجيحات الفقهية فيه، وأهم أسباب اختلاف الاجتهادات بين وفاء الضمانة وشرح النيل هو اطلاع المؤلف على نصوص الأحاديث من كتب السنة بعد الفراغ من تأليف شرح النيل، ولم تتأثر الفروع الفقهية الإباضية كثيرا بالانفتاح على كتب السنن والصحاح الأخرى عند غير الإباضية
Keywords: Atfiyyash, Muhammad b. Yusuf (1821-1914); Fiqh -- Mzab -- 19e siècle

God's Laborers: Missionary Work and Imperialism in the Congo From 1878-1908 - Peterson, Ana (Utah State university, 2024)
In 1878, Henry Craven opened the first Protestant mission in the Congo. The Livingstone Inland Mission created multiple stations along the Congo River to reach the interior. It stayed active for six years before transferring its stations to Swedish and American missions. Five years after its closure, a sister mission, the Congo Balolo Mission, resumed efforts to teach the people living in the interior. This thesis explores the evolving reaction of the missionaries to state violence. It argues that these missionaries initially supported imperial violence that enforced laws that aligned with their beliefs, such as removing the slave trade. Once that violence extended to profits alone and increased in violence, the missionaries joined the movement to improve conditions in the Congo.
Keywords: Esclavage -- Zanzibar; Tippo Tip (1837-1905)

The Wavering Power. The Portuguese hold on the Arabian coast of Oman 1622-1650 - Costa, Daniel Filipe Ferreira da (2021)
Portuguese presence in the Gulf of Oman developed, in general, since the early sixteenth century. However, the Arab shores were constantly side-lined in favour of Hormuz, the centre of Portuguese operations in the region. That changed in 1622, when the island was lost to an Anglo-Persian force. That moment, the Portuguese chose Muscat as a regional base and, as such, the Omani world became fundamental for the consolidation and enhancement of the Portuguese position as a leading power. Yet, the rule of the Omani shores proved to be difficult and hazardous. The Estado da India’s decline in resources, increasing European competition and the rise of a new united Arab entity exacerbated those difficulties and, in a few decades, Portuguese control was reduced to Muscat itself. This study addresses some of the pivotal characteristics and events related to the Portuguese presence in the Arabian coast of Oman, from the loss of Hormuz to the fall of Muscat in 1650. Therefore, military operations, commercial undertakings, financial difficulties, political decisions, religious features and tense relations are at the centre of the narrative. This way, it would be possible to understand how the Estado da India elite in Goa and the Portuguese officials in Oman acted throughout this period. Portuguese-Omani interactions started well before 1622 and continued well beyond 1650, but the three decades addressed in this dissertation can be seen as their climax.
Keywords: Relations -- Oman -- Portugal

A Sea of Wealth: Sayyid Saʿid bin Sultan, His Omani Empire, and the Making of an Oceanic Marketplace - Roberts, Nicholas P. (University of Notre Dame, 2021)
This dissertation is a history of the Omani Empire focused primarily on the first half of the nineteenth century. I use the reign of Oman’s longest serving ruler, Saʿid bin Sultan (1804/6-1856), as a lens for highlighting the formative role the Omani Empire played in uniting the Atlantic and Indian Oceans into a shared oceanic marketplace, a crucial step in the emergence of modern global capitalism. It is based on archival research and published primary sources from throughout Oman, Zanzibar, India, France, the United Kingdom, and the United States. This work reveals the Omani Empire as a new, mostly overlooked space for seeing how entrepreneurs and statesmen combined imperial agendas, slave labor, and the singular pursuit of profit in uniting disparate markets into global circuits of exchange. Across six chapters, I unravel the process by which Zanzibar, the empire’s capital, became a monied metropolis bursting with entrepreneurs from throughout the world, trading in the most coveted consumer goods of the time. By using an oceanic framework, I bring into focus an entire history of empire and capitalism that has been largely overlooked by many Middle East and Islamic world historians because of a conventional adherence to terrestrial units of analysis. Most broadly, I aim to show how the makings of the modern world lie as much in places like East Africa and the Arabian Peninsula as in places like England or New England. Accordingly, I use the Omani Empire as a platform for arguing that the formation of global capitalism resulted from relatively new maritime markets throughout the Atlantic Ocean being incorporated into the longer standing Indian Ocean world.
Keywords: Vie politique -- Oman -- 1804-1856

العلاقة بين السلطة الفرنسية الاستعمارية وسكان وادي ميزاب من خلال اتفاقية الحماية 1853م - فـراحات, نصيرة; مخطاري, أحلام (جامعة ابن خلدون, 2024)
Keywords: Relations -- Mzab -- France

جرائد وصحف منطقة بني ميزاب ودورها في الحركة الوطنية (1900-1954) - ساخي, محمد; رحماني, علي (جامعة ابن خلدون, 2024)
Keywords: Journalisme -- Mzab

الاختلاف العقدي عند المسلمين بين القطع والظن أهل السنة والشيعة والإباضية نموذجا - بن دريسو, مصطفى (جامعة الأمير عبد القادر للعلوم الاسلامية, 2024)
Keywords: Religions comparées -- Ibadisme -- Chiisme

How will Oman’s post-oil transition affect government constraints and social rights in the country? - Papatheophilou, Simela (Ghent University, 2024)
Keywords: Vie politique -- Oman -- 2020-....

La Penisola Omanita tra Preistoria e Protostoria attraverso lo studio di una collezione di manufatti archeologici - Ziglio, Micol (Universita degli Studi di Padova, 2022)
reserved
Keywords: Archéologie -- Oman

The rise of an Ibadi religious revival movement and its impacts on the society and built environment in the Mzab (Saharan Maghrib, 1868-1914) - Kwan, Elisabeth (University of Cambridge, 2024)
This study is about the rise of a nineteenth century religious renewal movement among Ibadi Mzabis, a sectarian and Saharan community. It looks at how this group responded to the local effects of a re-globalising world and redefined its sectarian identity to strengthen itself. The movement, which I call the Ibadi Mzabi *nahḍa*, began in the late 1860s when the community was faced with multiple pressures leading to social division. A cosmopolitan network of merchant-scholars drew on ideas which were circulating among broader Arab-Muslim cultural, intellectual and other religious *nahḍa* movements at the time. Some of these ideas shaped the way in which this local movement was expressed in its textual and built works. During a period of pressure in the 1870s and 1880s, there was a rise in the production of new texts. Through these new texts, there was a renewal of Ibadi religious law and rise in the authority of Ibadi religious scholars, and an increasing recognition that Mzabis were Ibadis rather than Kharijis. In Ghardāya, this rise in sectarianism resulted in the suppression of religious diversity in the public sphere and encouraged the integration of Muslims of multiple identities into a common and "renewed" Ibadi Mzabi community. During a period of prosperity and stability in the late 1890s, new commemorative shrines were built as part of this Ibadi Mzabi *nahḍa*. Through these shrines, new ideas of sectarian identity were expressed in the landscape, substantiating the historical legacy of contemporary Ibadi scholars and expressions of Ibadism in the Mzab.
Keywords: Réformisme -- Mzab

The separation of Oman and Zanzibar after 1856: British imperial policy, two Arab states and their elites - Żbik, Sebastian (2024)
Keywords: Vie politique -- Zanzibar -- 1856-1870

العلاقات العلمية بين جزيرة جربة ووادي ميزاب فيما بين القرنين (13/10ه16/19م) - يحي, بوشن (جامعة غرداية, 2024)
Keywords: Relations -- Djerba -- Mzab

The Process and Limits of Small State Neutrality: The Case of Oman between 1980 and 2022 - Abri, Omran Mohammed Zahran al- (University of York, 2024)
This thesis aims to provide a nuanced explanation of the birth, evolution and consistency of Oman’s foreign policy of neutrality. Over the last five decades, neutrality has been a core feature of Omani foreign policy. Departing from its Arab Gulf Neighbours, Oman decided to adopt neutrality in various conflicts such as the Iran-Iraq War in 1980–88, the Syrian Civil War and the recent War in Yemen, 2015–2022. Even in conflicts where it could not be neutral, Omani leaders would express their preference to maintain a neutral stance. To guide my analysis, I developed a conceptual framework, which I denominate as the processual model of neutrality (PMN), that conceives neutrality as a process of three phases: ‘strategic’, where the country decides to adopt neutrality for strategic reasons; ‘passive’, when the country adopts neutrality but lacks the recognition of external powers; and ‘active’, when the country adopts neutrality and has wide recognition for this policy, enabling it to play active neutral roles such as hosting peace negotiations and supporting humanitarian efforts. On this basis, this dissertation explores Omani foreign policy towards two major conflicts, the Iran-Iraq War (1980–1988) and the War in Yemen (2015–2022), demonstrating that these cases are crucial to understanding the emergence of Omani neutrality and its consolidation and recognition. Furthermore, this thesis explores the period between 1988–2015 in order to scrutinise how the Omani position varied during other major conflicts, such as the Iraqi invasion of Kuwait in 1990, the invasion of Afghanistan in 2001, the invasion of Iraq in 2003 and the Syrian Civil War in 2011. Using data drawn from interviewing key Omani decision-makers and visiting several archives in the UK, US and Oman, this thesis concludes that Oman’s neutrality started as a strategic decision resulting from a complex interaction of different domestic and external factors during the Iran-Iraq War. This thesis also argues that Oman was not able to adopt neutrality in cases such as the Iraqi invasion of Kuwait in 1990, the invasion of Afghanistan in 2001 and the invasion of Iraq in 2003 due to various reasons, including the influence of its security guarantors and serious threats perceptions. Finally, factors such as the wide recognition of Omani neutrality and diplomatic reach enabled Oman to exercise active neutrality during the War in Yemen.
Keywords: Politique étrangère -- Oman -- 1970-2020

الشيخ محمد بن أبي القاسم المصعبي وآثارة العلمية والاجتماعية بوادي مزاب (1045-1129 هـ/ 1635-1716 مـ) - محمد, أمسيرد; عبد الهادي, عوف (جامعة غرداية, 2024)
يعد موضوع دراسة تراجم وسير الشخصيات التاريخية العلمية الفاعلة في مجتمعاتها ,العمود الفقري لتقييم وتقويم المسار الحضاري لتلك المجتمعات ,وموضوعنا عن شخصية الشيخ محمد بن أبي القاسم بن يحي المصعبي الإباضي الجزائري (ت:1129ه/1716م) من تلك الشخصيات البارزة بوادي مزاب الذي عرف بتنظيماته الدينية على رأسها هيئة العزابة وغيرها , التي كان لها تأثيرا مباشرا في النشأة العلمية والاجتماعية التي أوصلته ليتصدر مشيخة الوادي و يعرف في الأقطار البعيدة كوارجلان و جربة و عمان وهذا ما انعكس فيما ترك من بصمات واضحة وآثار راسخة في المجال العمراني بإبداعه وتطويره لنظام فريد من نوعه عالميا وهو نظام تقاسيم مياه السيول بواحات قصر غرداية, بالإضافة الى ما ترك من إرث ثقافي متجذر في الذاكرة الجماعية للمجتمع المزابي الذي يظهر في بعض المناسبات الدينية والاجتماعية ,كما أنه برز في الجانب العلمي بما ترك من تراث قيم في عدة مجالات ما يزال أغلبه مخطوطا, وأفواج من الطلبة المتخرجين على يده من مختلف قصور وادي مزاب التي ساهمت في إعادة بعث الروح العلمية و العمل الاجتماعي بها. إن مكانته العلمية و الاجتماعية أهلته للتصدي للأخطار المحدقة بالوادي من فتن داخلية و تهديدات خارجية .The study of the translations and biographies of influential historical scientific figures in their societies constitutes the backbone for evaluating and assessing the civilizational trajectory of those societies. Our focus is on the personality of Sheikh Muhammad ibn Abi al-kacem ibn Yahya al-Mus'abi al-Ibadi algerian (d. 1129 H/1716 G), one of the prominent figures of Wadi Mzab known for his religious organizations, including the Azaba Council and others. These organizations had a direct impact on the scientific and social development that led him to lead the leadership of the valley. He was known in distant regions such as Warjilan , Jerba, and Oman, which is reflected in the clear imprints and entrenched effects in the urban field through his creativity and development of a unique global system, namely the system of dividing flood waters in the oases of Ghardaia Palace. Additionally, his cultural legacy rooted in the collective memory of the Mzab society appears in certain religious and social occasions. He also excelled in the scientific aspect through the valuable heritage he left in several fields, most of which are still manuscripts, and through the waves of students graduating under his guidance from various palaces of Wadi Mzab, contributing to reviving the scientific spirit and social work therein. His scientific and social status qualified him to confront the dangers facing the valley from internal seditions and external threats.
Keywords: Mzab -- Histoire -- 1510-1830; Vie intellectuelle -- Mzab

الضوابط الفقهية لاطفيش في شرح النيل (كتاب البيوع) - ورغ, سعيد صالح عمرو (جامعة غريان, 2024)
Keywords: Atfiyyash, Muhammad b. Yusuf (1821-1914); Fiqh -- Commentaires -- 19e siècle

عقيدة البعث من خلال سورة البقرة - مصباح, نور الدين (جامعة غرداية, 2024)
Keywords: Coran -- Commentaires -- 2000-....

The rise and decline of the island territories of Muscat and Oman in East Africa as a result of Great Britain's expansion in the region: A historical regional analysis (from the mid-19th to the mid-20th centuries) - Akovlevna, Malinina Ekaterina (Saint Petersburg State University, 2024)
Политика Великобритании с середины XIX века до середины XX века в Восточной Африке определялась экономическими и политическими интересами страны. Великобритания в этот исторический период имела своей целью сохранить господство в Индийском океане и контролировать все возможные пути в Индию. Основной деятельностью британского консула на Занзибаре в XIX веке была борьба с работорговлей: внимание британской общественности к это проблеме было привлечено исследованиями Ливингстона, Бертона, Спика в 1850-1860 гг . Несмотря на активную деятельность британских консулов в решении вопроса по отмене работорговли, договоры, заключаемые с султаном и запрещающие вывоз рабов с Занзибара и Килвы не соблюдались местным населением. Так, с одной стороны, британское правительство под давлением общественности желало полностью пресечь работорговлю в Восточной Африке, с другой стороны, оно не оказывало никакой поддержки чиновникам на Занзибаре, не желая брать на себя излишнюю ответственность. В конце XIX века во время активных притязаний европейских держав на территории в Восточной Африке, Великобритания продолжала политику «неопределенности» в отношении территорий владений султана, теряя свои позиции в регионе. С установлением в 1890 году протектората над Занзибаром, важным шагом в защите своих интересов в Восточной Африке, аболиционисты по всему миру требовали британское правительство отменить работорговлю на Занзибаре, который теперь находился под британской короной. В XX веке Великобритания европеизировала административный аппарат управления на Занзибаре, проводила судебные и финансовые реформы, используя политику косвенного управления и опираясь на арабскую знать, что, в конечном итоге, привело к формированию в обществе двух враждебных друг другу группировок: африканского большинства, не имевшего политических прав, и арабского меньшинства, обладавшего всеми правами; что впоследствии стало причиной Занзибарской революции в 1964 году. Целью данный работы является выявление ключевых причин постепенного падения влияния султана Омана в Восточной Африке и важных аспектов британской политики, которая привела к свержению султана в 1964 году в ходе Занзибарской революции. Для достижения вышеуказанной цели необходимо выполнить задачи, лежащие в разных тематических плоскостях. Первая глава будет посвящена описанию положения Занзибара в британской политике к середине 19 века. Во второй главе будет рассмотрено влияние британской политики по борьбе с работорговлей на позиции султана и продвижение британских интересов в регионе. В третьей главе будут выявлены причины уступок Великобритании Германии в Восточной Африке. Наконец, в четвертой главе будут рассмотрены причины свержения власти султана в 1964 году. Тема ВКР актуальна для формирования всеобъемлющего взгляда на становление международных торговых взаимоотношений в 19-20 веке, и позиций Восточно-Африканского региона в британской политике в указанный исторический период.
Keywords: Relations -- Oman -- Royaume-Uni

التوافق الاباضي المالكي في كل من ورقلة وتقرت وغرداية وما جاورها خلال العهد العثماني (دراسة استقصائية) - رويضة, مريم; بلغيث, حبيبة (جامعة غرداية, 2024)
Keywords: Ibadisme -- Ouargla

Étude des matériaux et techniques de réhabilitation de la place du marché de Ghardaïa - Heriz, Ameur; Houdjedje, Hammou (Université de Ghardaia, 2024)
Keywords: Architecture -- Mzab

حلقة العزابة وعلاقتها بالأنساق الاجتماعية تحليل محتوى خطابات الشيخ بيوض (حلقة عزابة القرارة نموذجا) - إبن يامي, عبد العزيز (جامعة غرداية, 2024)
Keywords: Bayyūḍ, Ibrāhīm ibn ʿUmar (1899-1981); Vie sociale -- Mzab

Etude des activités biologiques d’une plante aromatique médicinale - Nasri, Kaoutar; Lebouabi, Zineb (Université de Ghardaia, 2024)
Keywords: Botanique -- Mzab; Eucalyptus globulus -- Mzab

Solar PV and battery storage feasibility integration in Africa - Taking Djerba as a case study - Haddad, Alexander (University of Oslo, 2024)
Keywords: Energies renouvelables -- Djerba

التفاعل الرمزي في رواية "سيدات القمر" لجوخة الحارثي بنظرية جورج هربرت ميد - Pradani, Sefyra Adienda Putri (2024)
مستخلص البحث رواية "سيدات القمر" (في النسخة الإنجليزية تعرف ب "Celestial Bodies") لجوخة الحارثي نوع من أنواع الرواية التاريخية والاجتماعية، التي تقدم الصورة المتعمقة عن جهود المرأة العمانية في طلب الميزان بين التقليد والتحديث. إن الحضارة العمانية، التي قد تأثرت بالقيم التقليدية والأبوية، بدأت تواجه موجة التحديث، التي تجلب تغييرات في مختلف جوانب الحياة، بما في ذلك دور ومكانة المرأة في السعي لتحقيق الحرية والمعادلة. وراء ذلك، تكشف هذه الرواية أيضًا عن ديناميكيات الأسر والمجتمع في مواجهة التغيير الاجتماعي. يهدف هذا البحث إلى وصف حضارة وحياة المرأة العمانية كما تفسرها مفهوم العقل والذات والمجتمع في رواية "سيدات القمر" لجوخة الحارثي. باستخدام نظرية التفاعل الرمزي لجورج هربرت ميد، يركز هذا البحث على التفاعلات بين الأفراد والمجتمع، مما يؤكد الفهم من وجهة نظر الذات في استخدام الرموز التي تشير إلى المعنى نتيجة تفسيرها. وتظهر نتائج هذا البحث أن هناك ثلاثة مبادئ تظهر في مفهوم العقل، وهي مرحلة الرمز، ومرحلة تفكير المعنى، ومرحلة الإيماءات؛ أربعة مبادئ تظهر في مفهوم الذات، وهي الأنانية، واحترام الذات، والصورة الذاتية، و"I"/"Me"؛ وثلاثة مبادئ تظهر في مفهوم المجتمع وهي ظهور التعاطف والصراع والتجربة. ABSTRACT The novel “Sayyidat al-Qamar” (in the English version known as “Celestial Bodies”) by Jokha al-Harthi is a historical fiction and social realism genre novel that presents an in-depth portrait of the struggle of Omani women in finding a balance between tradition and modernization. Omani civilization, which was once heavily influenced by traditional and patriarchal values, is slowly starting to face the wave of modernization which brings changes in various aspects of life, including the role and position of women in the pursuit of freedom and equality. Apart from offering a picture of individual struggles, this novel also reveals the dynamics of families and communities in facing social change. This research aims to describe the civilization and life of Omani women as interpreted in the concepts of mind, self and society in the novel “Sayyidat al-Qamar” by Jokha al-Harthi. By using the theory of symbolic interactionism by George Herbert Mead, this research focuses on interactions between individuals and groups which emphasizes understanding from the subject's point of view in using symbols that indicate meaning as a result of their interpretation. This research results show that there are three principles that emerge in the Mind concept, namely the symbol stage, meaning thinking, and gesture stage; four principles that appear in the concept of Self, namely ego, self-esteem, self-image, and “I”/”Me”; and three principles that emerge in the concept of Society, namely the emergence of sympathy, conflict and experience. ABSTRAK Novel “Sayyidat al-Qamar” (dalam versi Inggris dikenal sebagai “Celestial Bodies”) karya Jokha al-Harthi merupakan sebuah novel bergenre fiksi sejarah dan realisme sosial yang menyajikan potret mendalam perjuangan wanita Oman dalam mencari keseimbangan antara tradisi dan modernisasi. Peradaban Oman, yang dulunya sangat dipengaruhi oleh nilai-nilai tradisional dan patriarkial, perlahan mulai menghadapi gelombang modernisasi yang membawa perubahan dalam berbagai aspek kehidupan, termasuk peran dan posisi wanita dalam mengejar kebebasan dan kesetaraan. Selain menawarkan gambaran terkait perjuangan individu, novel ini juga mengungkapkan dinamika keluarga dan komunitas dalam menghadapi perubahan sosial. Penelitian ini bertujuan untuk mendeskripsikan peradaban serta kehidupan wanita Oman yang terinterpretasikan dalam konsep pikiran (Mind), diri (Self), dan masyarakat (Society) dalam novel “Sayyidat al-Qamar” karya Jokha al-Harthi. Dengan menggunakan teori interaksionisme simbolik oleh George Herbert Mead, penelitian ini berfokus pada interaksi antar individu maupun kelompok yang menekankan pada pemahaman dari sudut pandang subjek dalam menggunakan simbol-simbol yang menunjuk makna sebagai hasil interpretasinya. Hasil penelitian ini menunjukkan bahwa terdapat tiga prinsip yang muncul dalam konsep Mind, yaitu tahap simbol, pemikiran makna, dan tahap gestur; empat prinsip yang muncul dalam konsep Self, yaitu ego, harga diri, citra diri, dan “I”/”Me”; dan tiga prinsip yang muncul dalam konsep Society, yaitu munculnya simpati, konflik, dan pengalaman.
Keywords: Littérature -- Oman

فعاليّة النّظام التّربوي وإعادة إنتاج قيم مجتمع الأم : دراسة ميدانيّة لمجموعة من المدارس الحرّة خارج وادي مزاب - عيسى, حمو عبد الله (جامعة مولود معمري, 2024)
تندرج هذه الدراسة الموسومة بـ "فعاليّة النّظام التربويّ وإعادة إنتاج قيم مجتمع الأمّ –دراسة ميدانيّة لمجموعةمن المدارس الحرّة خارج وادي مزاب-" ضمن تخصص علم اجتماع تربوي، والتي تهدف إلى: محاولة التعرّف على مجمل المدارس الحرّة المزابيّة خارج مزاب في العصر الحاضر، والكشف عن دور المدرسة في إعادة إنتاج القيمالاجتماعيّة و الوقوف على مدى تأثير الفكر الاستراتيجي للمدير في إعادة إنتاج قيم مجتمع الأم.كذلك الوقوف على مدى تأثير طرق التدريس التي يمارسها أستاذ المدرسة الحرّة المزابيّة خارج مزاب على إعادة إنتاج قيم مجتمع الأم. ومدى تأثير التزام الأستاذ بالقيمالاجتماعيّة في إعادة إنتاج قيم مجتمع الأم.لتحقيق هذه الأهداف تمّت صياغة التساؤل الرئيس التالي: " إلى أي مدى تؤثر فعاليّة النظام التربوي للمدارس الحرّة خارج وادي مزاب في إعادة إنتاج قيم مجتمع الأمّ؟" اعتمد الباحث في هذه الدراسة على المنهج الوصفي العلمي الذي يصف الظاهرة كما وكيفا وتمّ اعتماد الاستمارة كأداة رئيسة لجمع البيانات، والمقابلة كأداة مدعّمة. أجريت الدراسة على عينة متنوعة من مدراء ينسبة 15%، وأساتذة بنسبة 8.33%. وتلاميذ بنسبة 13.44%.، وقد تم اختيارهم بطريقة قصدية مجاليّة موزعين على (15) مدرسة حرّة. وخلصتالدراسة إلى النتائج التاليّة:  كلّما اتجهت القيادة التربويّة نحو التمسّك بالفكر الاستراتيجي كان إعادة إنتاج قيم مجتمع الأم أكثر ظهورًا.  كلّما كان الأستاذ أكثر التزامًا وتمسّكًا بقيم مجتمع الأم كان إعادة إنتاج قيم مجتمع الأم أكثر وضوحًا.  لا علاقة لطرق التدريس بالمقاربة بالكفاءات بإعادة إنتاج قيم مجتمع الأم في المدرسة الحرّة المزابيّة خارج مزاب.
Keywords: Enseignement -- Mzab

ترجيحات الشيخ الشماخي ( ت: 729هـ) في باب الصوم من خلال كتابه الإيضاح - برقيق, محمد مسعود جمعة (كلية العلوم الشرعية, 2021)
Keywords: Fiqh; Fiqh -- Traité

ترجيحات الشيخ الشماخي ( ت: 592) في باب الصلاة من خلال كتابه الإيضاح - شريحة, محمد موسى رمضان (كلية العلوم الشرعية, 2021)
Keywords: Fiqh; Fiqh -- prières

جوابات الإمام محمد بن محبوب - رحمه-: من كتاب جامع ابن جعفر (قسم الطهارات - الصلاة) - المحروقي, نصر بن حمد (كلية العلوم الشرعية, 2020)
Keywords: Fiqh; Fiqh -- prières

تحقيق: شرح القصيدة الحائية للشيخ محمد بن يوسف بن محمد المصعبي من الصفحة121 إلى نهاية الكتاب - الذهلي, حفص بن راشد (كلية العلوم الشرعية, 2023)
Keywords: Poésie -- Mzab

معالم الدين في الفلسفة و أصول الدين للشيخ عبد العزيز بن الحاج بن إبراهيم الثميني (ت: 1223هـ): من الصفحة ( 414) إلى الصفحة (454) - المقيمي, خالد بن بخيت (كلية العلوم الشرعية, 2020)

أراء القطب في مسائل الصلاة من خلال كتاب تيسير التفسير - ياسين, رضا خالد (كلية العلوم الشرعية, 2020)
Keywords: Fiqh; Fiqh -- prières

تحقيق مخطوطة ترتيب نوازل نفوسة للشيخ أمحمد بن يوسف أطفيش من صفحة 61-90 - أحمد, عبد الله بن يوسف (كلية العلوم الشرعية, 2023)
Keywords: Atfiyyash, Muhammad b. Yusuf (1821-1914); Fiqh -- Commentaires -- 19e siècle

تحقيق مخطوط ترتيب نوازل نفوسة للشيخ أمحمد بن يوسف أطفيش الصفحات 1-30 - التندميري, رمضان بن يوسف (كلية العلوم الشرعية, 2023)
Keywords: Atfiyyash, Muhammad b. Yusuf (1821-1914); Fiqh

تحقيق مخطوط ترتيب نوازل نفوسة للشيخ أمحمد بن يوسف أطفيش الصفحات 31-60 - عمرو, سليمان بن خليفة (كلية العلوم الشرعية, 2023)
Keywords: Atfiyyash, Muhammad b. Yusuf (1821-1914); Fiqh -- Commentaires -- 19e siècle

مصارف الزكاة وضوابطها في الفقه الإباضي: دراسة مقارنة - بورورو, الناصر بن إسماعيل (جامعة غرداية, 2023)
Keywords: Fiqh -- Zakāt

تجديد الفكر الاسلامي : مقاربات السنة و الشيعة و الاباضية و العلمانيين - جدي, وديع (كلية الآداب والعلوم الإنسانية, 2022)

اشكال التدين في نماذج السير الاباضية ببلاد المغرب حتى القرن العاشر الهجري / 16 ميلادي - فارس, محمد (كلية العلوم الانسانية والاجتماعية, 2022)

التربية المتحفية و دورها التربوي و الثقافي متحف جربة للتراث التقليي نموذجا - بن يونس, سرور; الجراي, أريج (المعهد العالي للغات بقابس, 2021)

تأثير التداخل اللغوي على التحصيل الدراسي جزيرة جربة نموذجا - السقالن, ريمة; تتوش, ملاك (المعهد العالي للغات بقابس, 2021)
Keywords: Linguistique -- Djerba

دراسة انثروبولوجية للتراث الغذائي ليهود جربة - عبد العزيز, امنة (كلية العلوم الأنسانية والإجتماعية, 2022)
Keywords: Judaïsme -- Djerba

بناء الهويات في سياقات انتقالية دراسة حالة هوية اصحاب البشرة السوداء بجزيرة جربة - المحمدي, رانيا (كلية العلوم الأنسانية والإجتماعية, 2022)

المعمورة كمزار عامي بجربة دراسة اثنوغرافية - بوعجيلة, غادة (كلية العلوم الأنسانية والإجتماعية, 2021)
Keywords: Croyances populaires -- Djerba; Moeurs et coutumes -- Djerba

التشغيل في القطاع السياحي : الواقع و الاشكاليات جزيرة جربة مثالا (2011-2020) - عويشاوي, نجم الدين (كلية العلوم الأنسانية والإجتماعية, 2021)
Keywords: Tourisme -- Djerba

Oman: Navigating Peace Amidst Turmoil - Liberti, Sofia (Taylor university, 2023)
This paper provides insight on the ways in which the country of Oman could be best equipped to foster peace in the Middle East based on their history and unique theological approach to Islam. It uses Yemen as a case study.
Keywords: Politique étrangère -- Oman -- 2020-....

الجغرافية التاريخية لمجالات بني توجين - عباد, محمود (جامعة الأمير عبد القادر, 2024)
ناقش هذه الأطروحة موضوعا يتعلق بالجغرافية التاريخية في جوانبه الخمسة : المجال العمران , المسالك . الطوبونيميا , والجماعات . ويمس هذا العمل المجال الجغرافي للونشريس وجنوبه وصولا إلى غاية تخوم الصحراء هذا وتظهر أهمية الموضوع في بحثه عن أهم المتغيرات التي شهدها المجال المطروق منذ نهاية الفترة القديمة وإلى نهاية العصر الوسيط , مستعينتا فيها بمنهجية ومقاربات تختلف عن سابقاتها من الدراسات التي إهتمت بتاريخ المجال أو بمجرد جهات وجوانب منه فقط , وبالإجمال فقد تطرقت إلى ستة فصول بحثية تحكمت في تحكمت فيها المعطيات المصدرية بشكل كبير فبينت المراكز الحضرية وحجم التطورات التي مستها على مختلف الأزمنة وبينت الحصون المنتشرة في المجال فقد حاولت التدقيق في مدى استمرارها وانقطاعها , وأيضا مراقبة تغيراتها الطبونيمية وحجم التأثير الذي خلفته عمليات التعريب التدريجي على سلامة أصولها القديمة ( الفنيقية , اللوبية , اللاتينية ) وهذا من حيث النطق والكتابة أو من حيث التحول لصالح استخدام أسماء جديدة , كما تناقش أيضا مدى تطور المسالك والطرق الطولية والعرضية في المجال , كما تسمح الدراسة بمعرفة التحولات التي شهدتها البنية الإجتماعية نتيجة التمييز الإثني ومايضاف إليه من الحروب والتحالفات ةالإقطاعات التي كانت في كل مرة تغير من خارطة التوطين وصولا في النهاية إليى نتيجة مباشرة توضح هجرة أو اندماج غالبية العناصر المحلية ( البربرية ) بعد هيمنة الجماعات العربية الهلالية على معظم المجال السهلي بداية من منتصف القرن الثامن للهجرة ( 14 م )
Keywords: Tribalisme -- Afrique du Nord

القضاء في عمان 1339-1390 هـ. = 1920-1970 م.: دراسة تاريخية - النبهانى, سالم بن حمد بن مرهون (جامعة السلطان قابوس, 2020)

إسهام المرأة في المجتمع العماني خلال القرون الستة الأولى للهجرة = السابع حتى الثاني عشر الميلادي - البلوشي, سناء بنت عبدالله بن مبارك (جامعة السلطان قابوس, 2020)

الإعجاز القرآني عند العوتبي من خلال كتابيه الضياء والإبانة - الراسبية, أسماء بنت سعيد (جامعة السلطان قابوس, 2020)
Keywords: Coran -- Commentaires

العلاقة السياسية بين العلماء والسلطة في عمان 1162 هـ. = 1749 م.-1331 هـ. = 1913 م. - السعدي, ناصر بن سيف (جامعة السلطان قابوس, 2020)

التعليل المصلحي في المذهب الإباضي: دراسة تأصيلية تطبيقية - الحوسني, هلال بن سليمان بن ذياب (جامعة اليرموك, 2020)

خلق الأفعال والكسب والاستطاعة عند الإباضية والمعتزلة: دراسة مقارنة - التوبي, منصور بن سعيد بن حمد (جامعة السلطان قابوس, 2020)
Keywords: Religions comparées -- Ibadisme -- Mutazilisme

Etude comparative de la dérivation en berbère (kabyle, tamazight du Moyen Atlas, touareg, mozabite et rifain) - Kardache, Sabrina; Khelifa, Danissa (Université Mouloud Mammeri, 2023)
Keywords: Linguistique -- Mzab

القضاء في عمان منذ دخولها الإسلام حتى أواخر القرن الثالث الهجري / التاسع الميلادي - الخاطرية, خلود بنت حمدان (جامعة السلطان قابوس, 2021)

نقد المتن عند الإباضية - العليمي, مصطفى بسام أحمد (جامعة آل البيت, 2021)

المذهب الإباضي في الأندلس وتأثيره السياسي على عهدي الدولة الأموية وملوك الطوائف - سونة, ماجدة (جامعة غرداية, 2021)

مفهوم اللقب وتطبيقاته في الفروع الفقهية في المذهب الإباضي: دراسة تأصيلية تطبيقية - الجهضمية, أنوار بنت زايد بن سليمان بن عبدالله (جامعة السلطان قابوس, 2022)

قياس الشبه عند الإباضية وتطبيقاته الفقهية: دراسة أصولية فقهية - الحضرمي, حمود بن عبدالله بن علي (جامعة السلطان قابوس, 2022)

L’ibāḍisme omanais : histoire et mémoire d’un mouvement dissident aux marges de l’Empire (IIe-VIe/VIIIe-XIIe siècle) - Baptiste, Enki (Université Lyon 2, 2023)
Keywords: Ibadisme -- Oman; Imamat -- Oman

L'aménagement urbain au M'Zab (Algérie) face aux enjeux du développement durable - Daddi Addoun, El Khoudir (Le Mans université, 2021)
Keywords: Urbanisme -- Mzab

مقارنة الخوارج عند شيخ الإسلام مع غيرهم من الفرق - جمعا ودراسةً - فرحات, عبد الرحمن (الجامعة الإسلامية بالمدينة المنورة, 2021)
Keywords: Kharijisme

التفسير المقاصدي عند الشيخ بيوض (ت 1041و/1891م) في تفسيره في رحاب القرآن - المقدمي, نادية عيسى خليفة (جامعة طرابلس, 2023)
Keywords: Bayyūḍ, Ibrāhīm ibn ʿUmar (1899-1981)

كتاب الأحكام للشيخ أبي زكرياء يحيى بن الخير الجناوني دراسة وتحقيق - ألدون, ربيع (جامعة الزيتونة, 2024)
Keywords: Fiqh; Fiqh -- Libye; Jannāwunī, Yaḥyā b. al-Khayr

منهج وآراء أبي عمار عبد الكافي الوارجلاني الاباضي (ت 570 ه) في رده على غير الإسلاميين من خلال كتابه الموجز - دراسة تحليلية - اولاد علي, محمد (جامعة الجزائر 1, 2023)
Keywords: Foi -- Traité -- 12e siècle

مظاهر الحياة الاقتصادية والاجتماعية لدى اباضية جبل نفوسة من القرن 4 ه/ 10م الي القرن 8ه/ 14م من خلال مخطوط كتاب اللقط لأبي عمران الشماخي - خليفي, حسين (كلية الاداب والعلوم الإنسانية بسوسة, 2023)
Keywords: Fiqh -- Libye

دراسة في المرتكزات والاثار للشفاعة عند الاباضية - عبد الرحماني, حسان (جامعة الجزائر 1, 2023)

النشاط الاقتصادي في الدولة الرستمية من خلال المصادر الإباضية سير الوسياني أنموذجًا (ق 6هـ–12م) - بركان, حدّة; مكلوش, فوزية (جامعة يحيى فارس, 2023)
ملخص إن الدولة الرستمية هي أول دولة خارجية تمتعت بالإستقلال فكانت هذه الدولة بالمغرب الأوسط أسسها عبد الرحمان بن رستم عام 161 ه /777م ،متخذا من تيهرت عاصمة. لها فقد لعبت تيهرت دورا متميزا في نمو و ازدهار النشاط التجاري بالمغرب الأوسط نظرا لموقعها الهام ،كما عرفت نشاطا اقتصاديا مزدهرا في شتى المجالات ،و قد روى العديد من المؤرخين الإباضيين على هذا النشاط الإقتصادي فكان من بينهم الربيع بن عبد السلام بن حسان بن عبد الله الوسياني ،و الذي كان من أبرز أعلام الإباضية . كانت بلاد المغرب الأوسط مزدهرة في المجال الزراعي فانتشرت البساتين و المزارع و ذلك راجع إلى كثرة تساقط كمية الأمطار و وفرة الموارد المائية و تنوعها من أنهار ،أبار ،عيون ،فتعددت المنتوجات الزراعية من حبوب و زيتون و نخيل و فواكه ،و بهذا أصبحت للأرض أهمية كبيرة في النشاط الفلاحي فقد تنوعت و اختلفت فمن أنواعها نجد :أراضي الإقطاع ،أراضي الملك ،و الأراضي الجماعية .كما سدت بهذه الدولة تربية المواشي و ذلك بسبب وجود المراعي الواسعة في السهول العليا و الجبال والتلال وعرفت العديد من الصناعات الحرفية و التي كانت تعتبر بمثابة النشاط الأساسي في المجتمع الرستمي و لعل من أبرزها الصناعات الزراعية ،صناعة الجلود ،النسيج ،الخشب.... إن بلاد المغرب الإسلامي ربطت علاقات تجارية مع جنوب الصحراء نظرا لتوفر العديد من المسالك و الطرق التجارية منها الطريق الغربي و هو من أقدم الطرق بالإضافة إلى الطريقين الشرقي و الأوسط و اللذان كان لهما دورا مهما في تجارة الرستميين مع بلاد السودان الغربي بحيث نتج عن هذه المسالك العديد من المراكز التجارية المغربية (سجلماسة ،واراجلان ، تاهرت ) ،و المغربية (أودغشت ،تادمكت ،وغاو ) ،فكانت تتم تبادل السلع و البضائع المختلفة بين الشمال و الجنوب في الأسواق و المدن ،و قد استخدمت الدولة الرستمية عددا من النظم في تجارتها الداخلية كالنقود و التي سهلت عملية التبادل التجاري. Summary The Rustamid state is the first foreign state that enjoyed independence, and this state was in the Middle Maghreb, founded by Abd al-Rahman ibn Rustam in the year 161 AH / 777 AD, taking Tihart as the capital. For her, Tehert played a distinguished role in the growth and prosperity of commercial activity in the Middle Maghreb due to its important location, as it knew a thriving economic activity in various fields, and many Ibadhi historians narrated this economic activity, among them was Al-Rabi bin Abd al-Salam bin Hassan bin Abdullah Al-Ossiani, who was one of the most prominent Ibadi flags. The countries of the Middle Maghreb were prosperous in the agricultural field, so orchards and farms spread, and this is due to the large amount of rainfall and the abundance of water resources and their diversity from rivers, wells, eyes, so the agricultural products multiplied, such as grains, olives, palm trees and fruits, and thus the land became important Great in agricultural activity, it varied and differed. Among its types, we find: feudal lands, king lands, and communal lands. This country also dominated livestock breeding, due to the presence of wide pastures in the upper plains, mountains, and hills, and it knew many craft industries, which were considered as The main activity in the Rustam community, perhaps the most prominent of which is the agricultural industries, the manufacture of leather, textile, wood.... The countries of the Islamic Maghreb linked commercial relations with the south of the Sahara due to the availability of many trade routes and routes, including the western route, which is one of the oldest roads, in addition to the eastern and central routes, which had an important role in the trade of the Rustamids with the countries of western Sudan, as a result of these routes Many Moroccan commercial centers (Sijlmassa, Argalan, Tahert), and Moroccan (Audghest, Tadamukt, and Gao), so different goods and merchandise were exchanged between the north and the south in the markets and cities, and the Rustamid state used a number of systems in its internal trade Like money, which facilitated the process of trade.
Keywords: Dynastie rustumide

تاهرت من سقوط العاصمة إلى زوال العمران 296-612 ه/909-1216 م - نوار, شريفة; حمو, شيماء (جامعة ابن خلدون, 2021)
سقطت تاهرت الرستمية على يد الشيعة الإسماعيلية سنة 296 ه/ 909 م، فخربت المدينة وأحرقت وقتل ممن كان بها من الرستميين ومن بقي فر إلى مناطق الدعوة الإباضية بورجلان، فأصبحت تاهرت ولاية تابعة للدولة العبيدية يحكمها والي شيعي. لكن أهل تاهرت من قبائل زناتة لم يرضوا بهذا الكيان السياسي الجديد، فقاموا بعمليات تمردية وثورات تعلن رفضهم لهذا الوجود الشيعي ، فإنعكست هذه الأعمال بالسلب على عمران المدينة... استمرت النكبات على تاهرت فظهرت صراعات قبلية بين زناتة وصنهاجة فإزدادت الأوضاع سوءا على عمرانها فغابت المدينة على الأحداث الحضارية بسبب مامر عليها من أحداث. بعد هذا شهدت تاهرت تخريبا اخر في العهد الموحدي وذلك نتيجةصراعها مع المرابطين على ارضه واعتبرت هذه الوقعية آخر وقعية لتاهرت سياسيا وحضاريا..
Keywords: Urbanisme -- Tahert

الأدوار السياسية والمذىبية لقبيلة هوارة في الغرب الإسلامي في العصر الوسيط - بن عبد المؤمن, سارة مروى (جامعة ابن خلدون, 2022)
تعالج هذه الدراسة الأدوار السياسية والمذهبية لقبيلة هوارة البرنسية في العصر الوسيط في الغرب الإسلامي، معرجة على مختلف المساهمات السياسية لهذه القبيلة وأهم الدول و الكيانات السياسية التي أسستها ،وإبراز مظاهر قوة و ضعف هذه القبيلة ،وكذا إسهامات علماء و فقهاء القبيلة في حياة المذهبية و الفكرية على حد سواء .

الدعوة الإباضية ببلاد المغرب خلال الفترة (100-150هـ) من خلال كتاب السير لأبي سعيد الشماخي - حاجي, فضيلة; تبرور, مباركة (جامعة يحي فارس, 2020)

الاجتهاد المقاصدي عند الإباضية في باب الأحوال الشخصية - الصادق, ياسين بن أحمد (جامعة غرداية, 2022)
لقد حاول الباحث في هذه الدّراسة البحثَ في جانب الفِكْرِ المقاصديّ للإباضيّة في باب من أبواب الفقه؛ حيث حاول الإجابةَ عن مدى توظيف عُلماء الإباضيّة للنّظر في المقصد، والكشف عن الحِكمة، واستنباط المصلحة من إقرار الْحُكم الفقهيّ أو توجيهه في مسائل الأحوال الشّخصيّة. وقامت أسسُه وارتكزت على بيان طرق تحقيق المقاصد الكليّة، واستندت على إيضاح وسائل تحصيل المصلحة الشّرعيّة، من خلال إقرار الأحكام الشّرعيّة العَمليّة، وبيان أثر ذلك على الفرد والأمَّة؛ وذلك في أبواب الأسرة والوصايا والمواريث والهبات والأوقاف. بناءً على ما تقدّم؛ فإنّه قد أجال النّظر في معالم الفِكر المقاصديّ، ومسالك النّظر الاستصلاحيّ لعُلماء المذهب، وأَعْمَل الفِكر في اجتهاداتهم واستنباطاتهم، وتحليلاتهم وتوجيهاتهم للأحكام الفقهيّة في باب الأحوال الشّخصيّة في ضوء المقاصد الكليّة والأهداف العامَّة للشّريعة الإسلاميّة، دون البحث في المقاصد الجزئيّة، وبعيدا عن كشف الأدلّة والمناهج الاجتهاديّة الأصوليّة، ووَفقا لهذه النّظرة واستنادا عليها تحدّدت معالم البحث وانبنت فصوله ومباحثه، وانتظمت تفاصيله وجزئيّاته. فجاءت المقاصد الكليّة الضّابطة لباب الأسرة مُتمثّلة في التعبّد والخشية لله، وحفظ النّسل، وتحقيق السّكن والاستقرار. وتمثّلت الأهداف العامّة الحاكمة لأبواب الوصايا والمواريث والهبات والأوقاف في التّقوى والْهُدَى، وإقامة العدل، وتحصيل المصالح ودرء المفاسد. وخَلُص البحث إلى أنّ جميع الأحكام إنّما شُرعت لحفظ الأمّة، وصَوْنِ نِظامها، وتحقيق التّكامل والتضامُن بين أفرادها، وَوِقايتها من اضطراب الحال، وحِراستها من سوء المآل.
Keywords: Ijtihad

نظرية المصلحة عند الإباضية وتطبيقاتها الفقهية من خلال آثار ابن بركة وأبي سعيد الكُدَمي - فخار, جابر بن سليمان (جامعة غرداية, 2022)
تطرُق الدراسة موضوعا أصوليًّا مقاصديا متجدِّدا، من زاوية تراثية، حيث تهدف إلى تقديم صورة شاملة عن نظرية الـمصلحة عند الإباضية من خلال نتاجهم الفقهي والأصولي، في بناء منهجي، محاولا استيعاب الـمفاصل الأساسية للموضوع عبر مسلك الاستقراء، وعرضها في أسلوب إقناعي يقوم على منهج التعليل والتدليل. ويحاول البحث الإجابة عن ثلاثة أسئلة رئيسة هي: ما أسس النظرية؟ ما هي قواعدها الـمنهجية؟ ما هي خططها الإجرائية؟ أما مفاصل الدراسة فهي تشتمل على فصل تمهيدي وخمسة فصول، ثم خاتمة تتضمن أهم النتائج الـمتوصل إليها؛ حيث احتوى الفصل التمهيدي على التعريف بشخصية الإمامين ابن بركة والكدمي من حيث مسيرتهما وآثرهما العلمية، مع الوقوف على أهم خصائص مدرستهما الفقهية. هذا، وتشترك الفصول الثلاثة الأولى في بحث أسس النظرية وقواعدها الـمنهجية؛ حيث خصص الأول لدراسة مصطلح الـمصلحة، والـمصطلحات ذات الصلة في التراث الفقهي، ثم سؤال الـمرجعية في إدراك الـمصالح. أما الفصل الثاني فتمحض لمسائل التعليل، وكان الفصل الثالث لدراسة علاقة الـمصلحة بالنص توافقا وتعارضا، مع بيان أهم الـمسالك الـمنهجية الكفيلة برفع التعارض، وتحقيق الانسجام والتكامل. وفي الفصل الرابع عرضٌ لموقف الإباضية من الأدلة الاجتهادية الـمبنية على الـمصلحة، تأصيلا وتطبيقا، وخُصِّص الفصل الأخير لموضوع فقه الـموازنات عند الإمامين، محاولا اكتشاف أهم قواعد الـموازنة والترجيح بين الـمصالح والـمفاسد. وقد أبانت الدراسة عن منطق البحث الفقهي لدى علماء الإباضية في التعامل مع الـمصالح والنصوص، حيث كان الاجتهاد الـمصلحي عموما قائما على أساس معقولية الأحكام ومصلحية التشريع جملة وتفصيلا، متخذا قواعد منهجية ضابطة للنظر العقلي، وخطط إجرائية كفيلة بسداد الفهم، وسلامة التطبيق لمقررات التشريع، بما يحقق مقاصدها الـمنشودة. كما كشفت الدراسة عن تميُّز كلٍّ من الإمامين بمنهج في الاستدلال بالـمصالح؛ حيث كان ابن بركة ينحو منحى التدليل القياسي تأييدا لاجتهاده الـمصلحي، مما يدل على هيمنة دليل القياس في فكره الفقهي، أما الكدمي فقد تميز بتلك العقلية الاستقرائية التي تتخذ من الـمعاني الكلية سندا في النظر الـمصلحي.
Keywords: Fiqh

كتاب "الإيضاح" للشيخ عامر بن علي الشماخي (ت 792هـ/1279م) -دراسة وتحقيق كتاب الشركة - الدبوز, حسن بن عيسى (جامعة غرداية, 2022)
يعتبر الشيخ عامر بن علي الشماخي (ت792هـ/1279م) أحد أبرز أعلام المدرسة الإباضية الذين ساهموا في مجال التأليف، مع قلة العناوين التي تركها، إلا أن كتابه "الإيضاح" برز بروزا واضحا في المذهب، فاهتم به الطلبة وأشاد به العلماء قديما وحديثا، واعتمده الفقهاء المغاربة مرجعا للفتوى في زمانه إلى يوم الناس هذا وفي مختلف حواضر الإباضية، كما اهتم به المشارقة كثيرا، وحظي بالاعتناء به حاشية واعتمادا وتلخيصا ونسخا وطباعة، إلا أنه لم يحظ بتحقيق علمي يبرزه كما ألَّفه مؤلفُه، ويكشف عن مكنوناته ومنهجه، ومن هذا المنطلق جاء هذا البحث لدراسة قسم من أقسامه وتحقيقه، تحت عنوان: كتاب "الإيضاح" للشيخ عامر بن علي الشماخي (ت792هـ/1279م) -دراسة وتحقيق كتاب الشركة- وفي هذا البحث تحقيق نص الكتاب بالمقارنة بين نسخه الخطية، وضبط نصه وخدمته، إلى جانب دراسة مضمون هذا النص لمعرفة منهج المؤلف في تأليفه، ودراسة مدى التزامه به في أبواب الكتاب، وبيان ما لم يذكره المؤلف من الجوانب المنهجية للكتاب من ذكر المصادر التي اعتمد عليه، وكذا منهجه في إقرار المسائل وأحكامها وما عليه العمل منها، ومنهج الاستدلال والتعليل في الكتاب.

سقوط مدينة تيهرت (296هـ/909م) وتداعياتها على الجماعات الإباضية - مصايف, نبيل; شيخ, بلقاسم (جامعة يحي فارس, 2021)

الفروق الفقهية عند الإباضية - علواني, إسماعيل بن إبراهيم (جامعة الحاج لخضر, 2022)
يتناول هذا البحث دراسة لعلم الفروق الفقهية عند الإباضية تنظيرا و تطبيقا، و هذا من خلال كتب أصول الفقه في المذهب الإباضي و استقراء الفروق الواردة في كتابي مدونة أبي غانم و جامع ابن بركة، متبعا في ذلك كله: المنهج الوصفي في المقدمات التنظيرية؛ و المنهج التوثيقي في جمع و تركيب الفروق المتناثرة في الكتابين؛ و المنهج التحليلي في تأصيل الفروق الفقهية في جانبيها التنظيري و التطبيقي و إثراء المسائل و مناقشتها . فجاء البحث مقسما على بابين؛ الأول خصصته للجانب النظري و دراسة منهج الفروق المستخلصة؛ و الثاني: ضمنته الفروق المستخرجة من الكتابين عينتي البحث، و تفرع عن كلا البابين ثلاثة فصول؛ فكانت فصول الباب الأول في بيان حقيقة الفروق الفقهية، و أهميتها و مراحل نشأتها، و تأصيلها الأصولي و الفقهي، مع عرضٍ لمناهج التفريق الفقهي و مسالك الكشف عن الوصف الفارق في كتب الفروق عموما، مرصعا هذا الباب بتوضيح منهج التفريق الفقهي عند الإمامين أبي غانم و ابن بركة من خلال كتابيهما المدونة و الجامع . و تناولت في فصول الباب الثاني من البحث مسائل الفروق المستخلصة من كتابي المدونة و الجامع، في جانب العبادات و الأيمان و النذور، و جانب العقود و المعاملات، و كذا مسائل القضاء و الدعاوى و الشهادات. و كللت الرسالة بخاتمة حاوية لأهم النتائج و التوصيات. و أهم ما يمكن أن نسجله من النتائج في هذه الدراسة : - بعد الاستقراء للفروق الفقهية الواردة في مدونة أبي غانم و جامع ابن بركة، خلصنا إلى أن الإباضية و إن لم يفردوا مصنفا خاصا بالفروق الفقهية و لا سفرا مستقلا في ذلك، لم يبسطوا القول في قواعده و أسسه، إلا أنهم عرفوا الكتابة في هذا الفن منذ عهدهم الأول كما تظهر ذلك الفصول التطبيقية في البحث، و هذا من خلال ما أودعوا في كتب الفروع من تفريقات دقيقة و تمييزات رشيقة. و الملاحظ من خلال فروق المدونة و الجامع أنها متركزة بشكل أكبر في قسم العبادات. كما أني من خلال هذا الاستقراء و التتبع لم أجد بين المصنفين منهجا متحدا في التفريق الفقهي، و ذلك للاختلاف في غرضهما من تأليف كتابيهما؛ بين من قصد بتصنيفه حفظ آثار العلماء من الاندثار فالتزم النقل الحرفي للأجوبة، و من سلك مسلك التأصيل و التحليل و المناقشة فلم يتقيد بذلك؛ و أضف إلى ذلك كون أبي غانم في بدايات عصر التدوين، بخلاف ابن بركة الموجود في عصر تمايزت فيه العلوم و تأسس معظمها. - إن الناظر في الاستدلالات الفرقية و الآليات المعتمدة في التفريق عند هذين العالمين يتبين له مدى رسوخ قدم علماء الإباضية في الفقه من أول أمرهم، كما أنه يقف على مدى توسعهم في الأخذ بالأدلة النصية و الاجتهادية، مما يجعل هذا المذهب مدرسة إسلامية أصيلة لازالت تحتاج إلى مزيد اعتناء و خدمة من الباحثين .
Keywords: Fiqh

التدين وعلاقته بالصلابة النفسية لدى المرأة الإباضية بمدينة ورقلة دراسة ميدانية على عينة من نساء الإباضيات بمدينة ورقلة - بومعقل, صفاء; باباحمو, دلال (جامعة قاصدي مرباح, 2020)
هدفت الدراسة إلى التعرف على علاقة التدين بالصلابة النفسية لدى المرأة الاباضية بمدينة ورقلة وذلك من أجل الإجابة عن التساؤلات التالية: • ما طبيعة العلاقة الارتباطية بين التدين والصلابة النفسية لدى المرأة الإباضية بورقلة؟ • هل توجد فروق دالة إحصائيا في مستوى التدين لدى المرأة الإباضية بورقلةبإختلاف السن؟ • هل توجد فروق دالة إحصائيا في مستوى التدين لدى المرأة الإباضية بورقلةبإختلاف المستوى الدراسي؟ • هل توجد فروق دالة إحصائيا في مستوى التدين لدى المرأة الإباضية بورقلةبإختلاف الحالة الاجتماعية؟ • هل توجد فروق دالة إحصائيا في مستوى الصلابة النفسية لدى المرأة الإباضية بورقلةبإختلاف السن؟ • هل توجد فروق دالة إحصائيا في مستوى الصلابة النفسية لدى المرأة الإباضية بورقلةبإختلاف المستوى الدراسي؟ • هل توجد فروق دالة إحصائيا في مستوى الصلابة النفسية لدى المرأة الإباضية بورقلةبإختلاف الحالة الاجتماعية؟ طبقت على عينة عشوائية مكونة من 107 امرأة إباضية بمدينة ورقلة في الموسم الدراسي 2019م /2020م. وقد استخدمت الطالبات مقياس التدين لزعطوط رمضان (2014) ومقياس الصلابة النفسية لمخيمر (2002)، وبعد تطبيق أدوات الدراسة، تم التحقق من صدقها باستخدام صدق المقارنة الطرفية، وكذلك الثبات بالتجزئة النصفية وألفا كرونباخ، ووجد بأن المقياسين صادقين وثابتيين وبالتالي صالحين لإجراء عملية القياس. وللوصول إلى نتائج الدراسة قامت الطالبات بمعالجة البيانات التي تم الحصول عليها باستخدام الأساليب الإحصائيةمن خلال الحزمة الاحصائية (SPSS) في نسخته رقم (23)، وقد توصلت الدراسة إلى النتائج التالية: -أن العلاقة بين التدين والصلابة النفسية لدى المرأة الإباضية بورقلة موجبة ومتوسطة وهي دالة إحصائيا عند مستوى 0،00. -لا توجد فروق دالة إحصائيا في مستوى التدين لدى المرأة الإباضية بمدينة ورقلة بإختلاف السن. -لا توجد فروق دالة إحصائيا في مستوى التدين لدى المرأة الإباضية بمدينة ورقلة بإختلاف المستوى الدراسي. -لا توجد فروق دالة إحصائيا في مستوى التدين لدى المرأة الإباضية بمدينة ورقلة بإختلاف الحالة الاجتماعية. -لا توجد فروق دالة إحصائيا في مستوى الصلابة النفسية لدى المرأة الإباضية بمدينة ورقلة بإختلاف السن. - توجد فروق دالة إحصائيا في مستوى الصلابة النفسية لدى المرأة الإباضية بمدينة ورقلة بإختلاف المستوى الدراسي. -لا توجد فروق دالة إحصائيا في مستوى الصلابة النفسية لدى المرأة الإباضية بمدينة ورقلة بإختلاف الحالة الاجتماعية.

L’État lecteur. Ethnologie de la vie intellectuelle au Sultanat d’Oman - Ayachi, Mehdi (Ecole des hautes études en sciences sociales, 2023)
Depuis la révolution de l’imprimé, introduit par les Omanais dans l’île de Zanzibar au tournant du XXe siècle, jusqu’à celle d’internet et des réseaux sociaux un siècle plus tard, l’émergence de la figure de l’intellectuel (al-muthaqqaf) semble liée à celle de la sphère publique, comprise comme le lieu où se médiatise la réflexion de la société sur elle-même. Ce travail de thèse, adossé à une enquête ethnographique de dix-huit mois, entend donc réfléchir la place et le rôle des intellectuels omanais contemporains au sein de la sphère publique, et ceci à l’aune du souci politique manifesté par l’État dynastique des Āl Sa‘īd pour « l’opinion publique » (al-ra’y al-‘ām) de sa population. Cette thèse propose ainsi une ethnologie de la vie intellectuelle au Sultanat d’Oman qui s’attache dans un premier temps à restituer la genèse et la structuration de cette sphère publique depuis la fin du XIXe siècle jusqu’à nos jours. L’étude des carrières et des sociabilités intellectuelles au sein d’un espace thématisé dans les termes conceptuels d’un « jeu intellectuel » permet, dans un deuxième temps, de réfléchir les conditions spatiales et matérielles de possibilité de la vie intellectuelle ainsi que ses limites, contrainte d’un côté par la répression politique de l’État et, de l’autre, par le contrôle social adossé aux logiques réputationnelles de l’honneur et de la honte, encore prééminentes dans une société tribale. Car qu’ils soient « traditionalistes » (taqlīdiyyīn), « rationalistes » (‘aqlāniyyīn) ou « libéraux » (lībrāliyyīn), qu’ils écrivent des romans, des poèmes ou des essais, les intellectuels omanais n’ignorent pas les limites qui restreignent l’acceptabilité de leurs discours et de leurs paroles dans la sphère publique. Ils savent que l’État omanais les surveille, les écoute, les lit, et que s’il rend en partie possible leurs carrières par la redistribution de la rente pétrolière sous la forme d’emplois publics, il les oriente aussi en retour, selon la logique de la gouvernementalité sultanienne de la main d’or et de la main de fer, qui réserve à chacun, selon sa loyauté, les plaisirs ou les peines, les rétributions ou les condamnations qui font respectivement « l’intellectuel d’État » (muthaqqaf sulṭawī) et « l’intellectuel critique » (muthaqqaf naqdī). La troisième partie de cette thèse permet cependant de voir comment certains intellectuels parviennent à inventer des espaces de liberté située et à visibiliser des orientations intellectuelles, religieuses ou politiques dans la sphère publique. Ce faisant, ils s’efforcent de penser l’historicité et la conflictualité politique de leur société en contradiction avec la vision d’une nation sans divisions, consensuelle et harmonieuse, qui est celle de l’idéologie de la naḥda (« la renaissance ») promue par l’historiographie officielle.
Keywords: Vie intellectuelle -- Oman

Günümüz Umman İbadi̇li̇ği̇nde Di̇ni̇ Tolerans Söylemi̇ - Bahadir, Lknur (Istanbul Üniversitesi, 2021)
The discourse of religious tolerance produced at the state level as a part of this incentive has been adopted by researchers working in the field and has become the main slogan that constitutes the content of activities promoting Oman at many levels today. This study, which examines the conditions for the formation of the religious tolerance discourse adopted by Oman and its current counterpart, consists of three parts. In the first part, the historical transformation of the imamate institution, which has an important place in the sectarianization process of Ibadi and which has created its existence as an independent structure from other sects, is emphasized. In the second part, the transformation of the struggle between imamate and sultanate into a power struggle as well as religious motivations and the capacity of the movements that took place outside the country to affect this struggle and its consequences are mentioned. In the third part, the discourse of religious tolerance, which was put into circulation with the beginning of the Sultan Qaboos period, and the concrete results of this discourse were evaluated.
Keywords: Tolérance religieuse -- Oman

İbâzî tefsirlerde Kur'an ilimleri = Qur'anic sciences in Ibāzî's tafsīrs - Altun, Fatih (Sakarya Üniversitesi, 2023)
Çalışmada, İbâzî müfessirlerin Kur'an ilimlerine yaklaşımlarının incelenmesi ve bu konulardaki görüşlerinin ortaya konulması hedeflenmiştir. Ulaşılan veriler Sünnî alimlerin görüşleriyle kıyaslanmıştır. Ayrıca İbâziyye'nin Hâricî bir fırka olup olmadığı da gözetilen hedeflerdendir. Çalışmada sekiz İbâzî müfessire ait on tefsir üzerinden Kur'an ilimleri tespit edilmiştir. Konu, Kur'an'ı tarih, lafız ve mana açısından inceleyen ilimler yönüyle ele alınmıştır. Tezin birinci bölümünde mezhebin ortaya çıktığı siyasî, dinî ve sosyal duruma, kısaca tarihine, Hâricîlerle ilişkisine, itikadî, siyasî ve halku'l-Kur'an görüşlerine yer verilmiştir. Bu bölümde İbâzî ve Sünnî kaynaklarla mezhep tanıtılmıştır. İkinci bölümde İbâzî müfessirler ve tefsir çalışmaları araştırılmış, İbâzî tarihi boyunca telif edilen tefsir eserleri ve müellifleri tanıtılmıştır. Üçüncü bölüm İbâzî müfessirlerin Kur'an ilimlerini ele alışlarına ve yorumlamalarına tahsis edilmiştir. Onların Kur'an ilimlerine bakışı ve bu ilimlerle ulaştıkları sonuçlar ortaya konulmuştur. Araştırma sonunda, ilk teşekkül döneminde Hâriciyye ve İbâziyye'nin seleflerinin aynı grup olduğu, İbâziyye'nin itikadî ve siyasî yönden Hâriciyye ile örtüşen ve örtüşmeyen görüşlerinin bulunduğu tespit edilmiştir. Yalnızca bu fikirler esas alınarak "İbâziyye, Hâriciyye'nin bir koludur" sonucuna varmak doğru bir değerlendirme olmaz. Hâricîlerin en belirgin vasıfları, kendileri gibi düşünmeyen dindaşlarına bakıştaki sert tutumlarıdır. Ötekine hayat hakkı tanımayan Hâricî anlayış, İbâzî tasavvurunda kabul görmemiştir. Mezhebî taassupla hareket etmeyen İbâzî müfessirler, oldukça geniş ve farklı mezheplere ait tefsir literatüründen beslenmiş; Kur'an'ın mesajlarını kapsamlı ve sahih olarak algılama, yorumlama ve onlardan hüküm çıkarmada Kur'an ilimlerini referans almışlardır. İbâzî müfessirlerin Kur'an ilimlerine yaklaşımı, genellikle Sünnî gelenekle benzer bir perspektif arz etmektedir.
Keywords: Coran -- Commentaires

Abbasi-Harici ilişkileri ve Kuzey Afrika`da kurulan Harici hanedanlıkları (Midrârîler, Rüstemîler) - Ay, Abdulhadi (Sosyal Bilimler Enstitüsü, 2020)
Bu çalışmada, Abbasi-Harici ilişkileri ve Kuzey Afrika'da kurulan Midrârîler ve Rüstemîler hanedanlıkları incelenmektedir. Bu tez çalışması; giriş ve dört bölümden oluşmaktadır. Çalışmanın giriş bölümünde konunun daha iyi anlaşılabilmesi için Haricilik, Hariciliğin ortaya çıkışını hazırlayan sebepler, temel görüşleri, karakteristik özellikleri ve fırkalara ayrılmaları, Afrika ve Mağrib'in coğrafi durumu, Midrârî ve Rüstemî Devleti'nin kuruluşundan önce Kuzey Afrika'nın durumu ele alınmıştır.Birinci bölümde Abbasi-Harici ilişkisi, Abbasiler dönemi Harici isyanları ve siyasi faaliyetleri üzerinde durulmuştur. İkinci bölümde tezin ana konusunu ihtiva eden ve Emevilerin Arap ırkçılığına karşı bir tepki olarak Harici Sufrilerin kurdukları Midrari Devletinin siyasi, sosyal, kültürel, ekonomik vs. yönleri ele alınmıştır. Üçüncü bölümde h.160/m.777 yılında Abdurrahman b. Rüstem tarafından kurulan Tahert merkezli Rüstemi Devleti'nin siyasi, sosyal, kültürel, ekonomik vs. yönleriyle ele alınmaya çalışılmıştır.Çalışmanın son bölümü olan dördüncü bölümde ise, Midrari Devleti ile Rüstemi Devletinin komşu devletlerle olan münasebetleri ele alınmıştır. Anahtar KelimelerHariciler, Abbasiler, Kuzey Afrika, Midrariler, Rüstemiler
Keywords: Dynastie rustumide

Ehl-İ Sünnet Ve İbâdi̇yye'ye Göre Hadi̇s-Ma'mer b. Râşi̇d'i̇n Câmi̇'i̇ (ö.153h./770) Ve Er- Rebî'b. Habîb'i̇n Müsned'i̇ (ö.171h./788) Örneği̇ - Alia, Sereen (İstanbul Üniversitesi, 2020)

İbâziyye'nin hadis anlayışı - Peker, Rabia (Bursa Uludağ Üniversitesi, 2020)
İbâziyye, Hâricî grupların içinde neşet etmiştir. Ehl-i Sünnet'e karşı muhalif olsalar da Hâricîler gibi aktif olarak savaşmayan, kuûdu tercih eden bir gruptur. Bu sebeple merkeze uzak dursalar da günümüze kadar ulaşmayı başaran bir gruptur. Ehl-i Sünnet'e ibadet ve itikatta olan yakınlıkları, Haricî bir gelenekten geliyor olmalarına rağmen mutedil anlayışları ve bir ilmi birikime sahip olmaları günümüze ulaşmasındaki diğer etkenlerdir. Ülkemizde ise bu mezhep hakkında yapılan çalışmaların azlığı dikkat çekmektedir. Ancak yapılan çalışmalar mezhebi daha yakından tanımak adına sürekli olarak artmaktadır. Bizim tezimizde bu çalışmalara katkı sağlamayı amaçlamaktadır. Tezimizde İbâzîler nezdinde en önemli fıkıh usulü kitabı olan el-'Adl ve'l-insâf 'ı inceleyerek hadis anlayışlarına dair geniş bir yelpaze sunmayı hedeflemekteyiz. Giriş kısmında mezhebin ortaya çıkışını, birinci bölümde hadis kaynaklarını ve devamında hadisi nasıl kullandığını göstererek hadis anlayışları ortaya konmaya çalıştık. Sonuç bölümünde de çıkarımlarımıza yer verdik.

La mémoire à travers l’histoire le puzzle de la mémoire en naufrage chez Slimane Benaissa : La triade de « Babour Ghraq» - Bourouis, Khalid; Semoum, Khireddine (Université Kasdi Merbah, 2022)
Le présent travail de recherche s’intitule la mémoire à travers l’Histoire : le puzzle de la mémoire en naufrage chez Slimane Baissa : la triade de « Babour Ghraq» vise à étudier comment Slimane BENAISSA, à partir de la tirade «Nâalbou li mayhebnach », est parvenu à construire et à transmettre la mémoire plurielle des algériens. Ce travail comporte deux chapitres, dans le premier nous abordons la représentation de l’auteur et ses œuvres, et dans le deuxième chapitre nous étudions les procédés et les stratégies textuelles et théâtrales de la construction et de la transmission de la mémoire que renferme cette tirade.
Keywords: Littérature -- Mzab

المنهج الفقهي لأبي العباس أحمد الفرسطائي (ت: 504هـ/1111م) - مصباح, عيسى بن باحمد (جامعة غرداية, 2020)
Keywords: Fiqh; Furṣuṭāʾī, Aḥmad b. Muḥammad

النشاط الثوري في غرداية في مواجهة الاستعمار الفرنسي في الجزائر 1956-1962 - بكار, الدهمة (جامعة غرداية, 2020)
Keywords: Mouvement national -- Mzab

جهود الدكتور إبراهيم بحاز في كتابة تاريخ المغرب الإسلامي - عمي سعيد, عبد الفتاح (جامعة غرداية, 2021)

التعليل عند الإباضية وأثره في الفروع الفقهية دراسة أصولية مقاصدية - تمزغين, يوسف بن علي (جامعة العلوم الإسلامية الماليزية, 2022)
Keywords: Fiqh -- Ibadisme

الترجيحات الفقيهة عند قطب الأئمة امحمد بن يوسف اطفيش في كتابه شامل الأصل والفرع - دراسة نماذج - كروم, سليمان (جامعة أحمد دراية, 2021)
Keywords: Atfiyyash, Muhammad b. Yusuf (1821-1914)

الملامح الفلسفية في علم الكلام الإباضي المغاربي القديم - عبد الرزاق, بلقاسم (جامعة الحاج لخضر, 2023)
الهدف العام من هذه الأطروحة هو القراءة الفلسفية لعلم الكلام الاباضي المغاربي القديم قراءة كمية غير تفكيكية ،و ذلك بالبحث عن النسق العام الذي يسير كل المقولات الكلامية في كل مسائل علم الكلام من دقيقة إلى جليلة ،و قد توصلنا إلى أن المبدأ الفلسفي الذي تنطلق منه كل الآراء الكلامية هو التوحيد المطلق بالمعنى الرياضي للكلمة ، فكل المسائل الكلامية على تعدد وحداتها لا بد من إرجاعها إلى الواحد المطلق، فالتوحيد الإلهي قائم على فلسفة الواحد في الصفات و الأفعال و الأسماء. و الإيمان الإنساني قائم على التوحيد بين القول و العمل، و العلاقات الإنسانية الاجتماعية قائمة على أساس اعتقاد الجميع بالتوحيد المطلق في الاعتقاد و في الفعل . ⵉⵙⵡⵉ ⴰⵢⵉⵀⴷⵉ ⵙⴳⵉ ⵀⵎⴻⵙⵙⴻⵔⵙⵉX ⵏⴻⵜⵜⴰ V ⴰⵖⵕⴰⵢ ⵉⵖⵉⵍⴰⵏ ⵉ ⵀⵎⵓⵙⵙⵏⵉ ⵏ ⵡⴰⵡⴰⵍ ⴰⵢⵉⴱⴰⴹⵉ ⴰⵎⵓⵔⵉ ⴰⴳⴱⵓⵔ ⴰⵖⵕⴰⵢ V ⵢⵉⵀⴷⵉ ⵍⵉⴷ V ⴰⵙⴻⵏⵚⴻⵍ,V ⵡⵉV-ⵉⵏ ⵙ ⵓⵏⵄⵉⵍⵉ ⴼ ⵓⵏⵃⴰⵃⴻⵛ ⵡⴰⴷ-ⵖ ⵉⵍⴰⵖⵖⴻⴹ ⵢⴻⵀⴷⵉ ⵏ ⵜⵎⴻⵏⵏⴰⵢⵉⵏ ⵀⵉⵎⵡⴻXⵍⴰⵢⵉⵏ ⴳⴳⵉ ⵀⵙⴰⵇⵙⵉⵡⵉⵏ ⵢⴻⵀⴷⵉ ⵏ ⵜⵎⵓⵙⵙⵏⵉ ⵏ ⵡⴰⵡⴰⵍ ⵙⴳⵉ ⵀⴰⵢ ⵣⴷVⴻⵏⵏ ⵖⴰⵕ Xⴰⵢ ⵀⴻⴱⵔⴻⵏⵏ,ⵡ ⴰⵏⵛⵏⵉ ⵏⴻⵡⵡⴻⴹ ⵖⴰⵔ ⴰX ⴰⵏⴻⵣⵡⴰⵔ ⴰⵖⵉⵍⴰⵏ ⴰⴷ-ⵖ ⵀⴻⵜⵜⴻⵏⵥⴰⵕⵕ ⵙⵙ-ⵉⵙ ⵀⵉⵥⴻⵕⵕⵉⵡⵉⵏ ⵀⴰⵡⴰⵍⵉⵢⵢⵉⵏ ⵏⴻⵜⵜⴰ V ⴰⵏⵡⵉⵛⴻⵜ ⴰⵎⴻⵍⵍⵓⴼ,ⵙ ⵓⵏⴰⵎⴻⴽ ⴰⵏⴻⵣⵡⴰⵍ ⵉ ⵡⴰⵡⴰⵍ,ⵡ ⵢⴻⵀⴷⵉ ⵏ ⵜⵙⴰⵇⵙⵉⵡⵉⵏ ⵀⵉⵏⵓXⵍⴰⵢⵉⵏ ⴼ ⵜⴰⴳⵉXⵉ ⵏ ⵜⵏⵓⵛⵜⵉⵡⵉⵏ ⵙ ⵓⵎⴻⵖⵢⴻⵍ ⵉ ⵀⵡⴰⵄⵉⵜⵜ-ⵏⵏⴻⵙ ⵉ ⵡⵡⵉⵛⴻⵜ ⴰⵎⴻⵍⵍⵓⴼ,ⵡ ⴰⵏⵡⵉⵛⴻⵜ ⴰⵢⴻⵍⵍⵡⵉ ⵢⴻⵏⴷⵓ ⴼ ⵜⵖⵉⵍⴰⵏⴻⵜ ⵏ ⵓⵡⵡⵉⵛⴻⵜ ⴳⵉ ⵀⵓⴽVⴰⵍⵉⵏ V ⵜⵉⴳⴰⵢⵉⵏ V ⵉⵇⵇⴰⵔⴻⵏ,ⵡ ⵀⵏⴻⴽⵔⴻⵙⵜ ⵀⴰⵎVⴰⵏⵉX ⵀⴻⵏⴷⵓ ⵊⴰⵔ ⵏ ⵡⴰⵡⴰⵍ V ⵡⴰⴳⴰⵢ,V ⵜⵓⵇⵇⵏⵉⵡⵉⵏ ⵀⵉⵎVⴰⵏⵉⵢⵢⵉⵏ ⵀⵉⵎⴰⴳⵔⴰⵡⵉⵏ ⵏⴷⵓⵏ-ⵜ ⴼ ⵜⵏⴻⴽⵔⴻⵙⵜ ⵏ ⵢⴻⵀⴷⵉ ⵙ ⵓⵏⵡⵉⵛⴻⵜ ⴰⵎⴻⵍⵍⵓⴼ ⴳⴳⵉ ⵀⵏⴻⴽⵔⴻⵙⵜ V ⵡⴰⴳⴰⵢ. L'objectif général de cette thèse est la lecture philosophique de l'ancienne théologie maghrébine Ibadite, une lecture non déconstructive , en recherchant le schéma général qui parcourt tous les énoncés théologiques dans toutes les questions de théologie du plus petit au plus grand, et nous avons conclu que le principe philosophique à partir duquel toutes les opinions théologiques sont le monothéisme absolu, au sens mathématique du terme, donc toutes les questions théologiques sur la pluralité de leurs unités doivent être ramenées à l'absolu Un. L'humanité sociale repose sur la croyance de chacun au monothéisme absolu dans la croyance et l'action.
Keywords: Foi -- Traité

رموز ودلالات شجرة الزيتون في جزيرة جربة - بن صالح, عماد (المعهد العالي للتنشيط الشبابي والثقافي, 2021)
Keywords: Moeurs et coutumes -- Djerba

‏هداية الرحمن الى ثبوت خلق القرآن تأليف الشيخ القاضي متصور بن ناصر محمد الفارسي (ت: 1396 / 1976م) دراسة وتحقيقها - الجابري, محمد بن خلفان (كلية العلوم الشعرية, 2022)
Keywords: Coran -- Commentaires

‏ترجيجات الشيخ الشماخي في باب الطهارات من خلال كتاب الإيضاح دراسة فقهية مقارنة - الجعفري, عبد الرؤوف أحمد (كلية العلوم الشعرية, 2022)
Keywords: Fiqh

Abū Isḥāq Aṭfayyiš eṭ la redéfinition de l’identité ibadite dans l’entre-deux guerres (1923-1939) : réformisme, communauté et pouvoir - Cernon, Baudouin de (Inalco, 2022)
Keywords: Aṭfiyyash, Ibrāhīm b. Muḥammad (1886-1965); Réformisme -- Mzab

Commerce d’êtres humains et projets coloniaux à Zanzibar et Kilwa : Étude de la traite négrière française à la côte swahilie et des relations diplomatiques liant Français, Swahilis et Omanais (1770-1859) - Belhacel, Abdelhakim (Université Paris Nanterre, 2022)
Keywords: Zanzibar

Étude critique des Voyages faits par le sieur D.B. De la circulation des informations et de l’échec de la première Compagnie des Indes Orientales à Madagascar - Belhacel, Abdelhakim (Université Paris Nanterre, 2020)
Keywords: Relations -- Oman -- France

Le Tafsīr de Hūd b. Muḥakkam al-Hawwārī (IIIe/IXe s.). Analyse d’un commentaire coranique ibadite - Khelifa, Ahmed (Université Lumière Lyon 2, 2022)
Ce travail de fin d’études pour l’obtention du Master est consacré à l’analyse d’un commentaire coranique peu connu, en l’occurrence, celui de Hūd b. Muḥakkam al-Hawwārī (m. v. 280/893), un exégète ibadite du IXe siècle. En effet, les études consacrées à la tradition exégétique ibadite se comptent sur les doigts d’une main d’où notre intérêt pour le sujet. L’objectif était de voir dans quelle mesure le commentaire de Hūd constitue le témoin d’une tradition exégétique proprement ibadite. A l’issue d’une analyse comparative avec un commentaire qui lui est antérieur à savoir le tafsīr de Yaḥyā b. Sallām (m. 200/815), un exégète de Baṣra qui a vécu à Kairouan à la fin de sa vie où il a diffusé son savoir religieux et notamment son commentaire coranique, qui a été utilisé ultérieurement par Hūd b. Muḥakkam, comme source principale pour réaliser un tafs īr abrégé compatible avec sa doctrine ibadite. Tel est le résultat que nous avons établi par une étude comparative intertextuelle entre les deux commentaires. De la même manière, la comparaison avec l’exégèse sunnite de Ṭabarī (m. 310/923), elle ne laisse aucun doute que l’abrégé de Hūd s’inscrit entièrement dans le cadre de la doctrine ibadite. Après avoir confirmé l’hypothèse formulée par l’éditeur du commentaire coranique à savoir que Hūd b. Muḥakkam s’est basé sur le tafsīr d’Ibn Sallām pour réaliser son commentaire exégétique, ce mémoire a permis également de déterminer la méthode exégétique de l’auteur ibadite qui a été basée essentiellement sur la séléction dans le commentaire source d’Ibn Sallām, des traditions jugées compatibles avec les fondements de son école ibadite et le rajout de quelques adaptations afin de rendre son commentaire conforme aux attentes de sa communauté.
Keywords: Coran -- Commentaires -- 9e siècle; Hawwārī, Hūd b. Muḥkim al-

كتاب النكاح للشيخ ابي زكرياء الجناوني (ق 5-6هـ/11-12م): دراسة وتحقيق من بداية الكتاب الى باب نكاح المتعة ونكاح الشعري - بكلي, إبراهيم (جامعة غرداية, 2022)
Keywords: Fiqh -- Libye -- 12e siècle; Jannāwunī, Yaḥyā b. al-Khayr

فهرسة مخطوطات مكتبة جامع الباسي بوالغ جربة.. مداخل في الكوديكولوجيا والفهرسة - الصيد, سميرة (المعهد العالي للعلوم الإنسانية بمدنين, 2021)
Keywords: Catalogue -- Djerba

دور مزاب في الحركة الوطنية الجزائرية والثورة التحريرية 1391 – 1391م - بوسعدة, محمد بن عمر (جامعة الشهيد حمه لخضر, 2020)
Keywords: Mouvement national -- Mzab

State building and state-society relations in Libya (1911-1969): An examination of associations, trade unions and religious actors - El Taraboulsi, Sherine Nabil (University of Oxford, 2020)
This thesis is an examination of state-society relations in Libya during the period preceding the rise of Gaddafi in 1969. It addresses the roots of Libya’s recurring state failure by examining the role played by Libyan social actors in state building during the period between 1911 and 1969. Three key periods in Libya’s history are addressed: the colonial period under the Italians (1911–1943), then the years under the British Military Administration (1943–1951) and then the period as an independent monarchy (1951– 1969). Three social actors are explored: associations or jamʿiyyat, trade unions, and religious groups. Based on Migdal (2004) and Saouli (2012), I approach state formation as a process, not as a finished outcome, and the state as a social field wherein social actors engage with one another as well as with state structures rather than a fixed entity. This approach allows a deeper understanding of the temporal dimensions of Libya’s experience with state building as well as the different processes at play through which states are formed and (un)formed. The thesis makes three key arguments. First, contrary to the majority of Western scholarship on Libya which ascribes Libya’s “statelessness” to a failure to adopt modern state formation following independence, I argue that this linear view oversimplifies a much more complex local power dynamic among social actors, and between social actors and the state (colonial and postcolonial) that manifested itself in modes of cooperation and contestation that shaped Libya’s experience with state building. This view of “statelessness” also suggests that divisions in Libya’s social fabric are endemic which is not the case. Through a social history of the period in question, the thesis shows that while contestation among social actors before and after independence had been stronger than centralizing forces, this should be explained in context and in history. Second, I argue that 8 within non-Western societies where a normative notion of the modern nation-state was imposed but was adopted by local actors and adapted to social, cultural and historical realities that are local, it is within the civic space that society was empowered to shape the state in both constructive and (de)constructive ways, and that there is a pattern to how this shaping happens that is embedded within the history of those societies. Third, the thesis demonstrates that Libya’s civic space has played a twofold role in state formation. On the one hand, it has actively contributed to the strengthening of resistance forces against colonialism, the development of state institutions and the domestication of state power as experienced in the Kingdom of Libya (1951 – 1969). On the other hand, because of societal differences, many of which resulted from aggressive colonialism, a short history of institutionalization and the entrenchment of fragmentation and regional differences, Libya’s civic space manifested processes of localism or bonding and coalescing that occurred within groups which compromised the development of a Libyan state as in the case of the Tripolitanian Republic (1918 – 1922). The thesis demonstrates that state building can be compromised by contested state-society relations and that a state in the making would need to incorporate various forms of its civic space within its bureaucracies and overall model of government to ensure its local legitimacy and geopolitical unity. Using a sociohistorical approach which includes primary data from archives in London, Rome and Tunis, as well as 80 semi-structured interviews, this research makes a contribution to a social history of twentieth-century Libya by exploring its civic space and its engagement with governing structures, colonial and independent

Assessment of the engagement of The White Fathers in Colonial Algeria at the end of the XIX century - Meghnine, Khaled (University of Birmingham, 2020)
Keywords: Missionnaires -- Mzab

مكتبات المخطوطات بجزیرة جربة مزارات ثقافیة سیاحیة: مكتبة جامع الترك أنموذجا - يزید, انتظار (المعھد العالي للعلوم الإنسانیة بمدنین, 2020)
Keywords: Bibliothèques -- Djerba

التأصيل للعمارن التقليدي وملامحه في التوسعات العمارنية الجديدة للمدن العتيقة الصحاروية قصر تافيلالت (بني يزقن)- واد مازب نموذجا - بن ساحة, فاطمة الزهرة (جامعة محمد بوضياف, 2021)

كتاب البحث الصادق والاستكشاف لأبي القاسم بن إبراهيم البرادي (حي في: 810ه) دراسة وتحقيق (من اللّوحة:1 إل: 201) - حشحوش, عبد الحفيظ (جامعة الزيتونة, 2021)
Keywords: Barrādī, Abū ‘l-Qāsim b. Ibrāhīm al-

Une approche de valorisation du patrimoine de l’île de Djerba - Berhouma, Farah (Ecole supérieur d'architecture d'audioviduel et de design, 2020)
L'approche de valorisation du patrimoine architectural et culturel installée dans les Menzels en ruine de l’île, d’une part, permettra certes de préserver ces ruines, d’autre part, permettra d’illustrer tout un patrimoine matériel de l’île et d’expliquer d’une manière vivante tous les détails s’y rapportant à l'intérieur d'un Menzel. Le projet sera un pôle d’attraction et de reconnexion tant à l’échelle nationale qu’à celle internationale, il sera un repère dans tout circuit visite de l’île .Son animation et sa vivacité lui attribueront toujours un air authentique et exceptionnel. Le rôle de cette intervention s'était encore plus loin. Elle sera une source d’inspiration pour toute tentative de développement local ou même national à travers une alternative qui associer une approche de sauvegarde intégrer associant une approche durable à toute intervention.
Keywords: Architecture -- Djerba

Souk Erbaa Jerba : Un lieu holistique - Gorai, Mayçène (Ecole nationale d'architecture et d'urbanisme, 2020)
Le présent mémoire porte sur la reconnexion du Souk Erbaa Jerba avec son voisinage à travers une écriture spatiale qui tente de restaurer le génie de ce lieu et retrouver son caractère holistique. Dans une perspective de résoudre les conflits entre le souk et son voisinage (les fondouks et les 3 places : Ben Yedder, Ben Daamech et Zarraa), nous essayerons de suivre l'évolution de la configuration et la conformation du souk pour comprendre les raisons derrière la synchronisation entre ces dernières pendant une temporalité passée et expliquer le décalage et la désynchronisation qui existent aujourd'hui entre la forme de l'espace commercial et la pratique commerciale. Dans notre quête de réconcilier le souk avec les fondouks et les places, nous cherchons à synchroniser de nouveau entre le cadre actoriel et le cadre actantiel du souk afin de réactiver le génie de ce lieu.
Keywords: Architecture -- Djerba

Towards Sustainable Water Management in Sohar, Oman - Schout, Gilian (Universiteit Utrecht, 2020)

فضاءات الاحتجاج وأنساقها الرمزيّة : مقاربة أنتربولوجية تأويلية لإباضية وادي ميزاب - بوفريخة, أسامة (جامعة سوسة, 2020)

Patrimoine et protection des mosquées ibadites de Djerba. L'action de l'Assidje (1965-2021) - Gouja, Yousra (Université Paris 1, 2021)
Keywords: Monuments -- conservation -- Djerba

Analyse du discours de chercheurs contemporains sur les mosquées ibadites de Djerba - Gouja, Yousra (Université Paris 1, 2020)
Keywords: Monuments -- Djerba

القواعد والضوابط الفقهية المستخرجة من كتاب الإيضاح للشيخ عامر بن علي الشماخي - ويرو, سعيد بن يحيى (جامعة أبي بكر بلقايد, 2021)
Keywords: Fiqh

الترجيحات الفقهية عند الشيخ امحمد بن يوسف أطفيش في كتابه شرح كتاب النيل.. دراسة في أبواب البيوع - بن لولو, اسماعيل بن موسى (جامعة غرداية, 2021)
Keywords: Atfiyyash, Muhammad b. Yusuf (1821-1914); Fiqh

القواعد والضوابط الفقهية للعمارة في الفقه الإباضي، كتاب القسمة وأصول الأرضين للشيخ أبي العباس أحمد بن محمد الفرسطائي نموذجا. - كعبوش, زكرياء بن قاسم (جامعة غرداية, 2021)
Keywords: Fiqh; Furṣuṭāʾī, Aḥmad b. Muḥammad

Les ksour de la Pentapole mozabite : pratiques anciennes et pratiques du présent - Bouchemal, Kaouthar (Université Paris 10, 2020)
Ce travail s’inscrit dans une problématique qui soulève la question des pratiques d’une société qui a su préserver son patrimoine vernaculaire et qui tente de le perpétuer. Ce dernier est constitué par les ksour, la forme d’habitat traditionnel au Sahara algérien. Datant de l’époque médiévale, ce patrimoine regroupe les cinq cités de la Pentapole de la vallée du M’zab, une contrée où habite une population musulmane ibadite formant une minorité religieuse. Dans cet endroit, la façon de construire d’autrefois, qui s’articule sur une organisation sociale basée sur l’intime et le sacré, n’a pas laissé insensibles de grands bâtisseurs, comme Le Corbusier, qui s’en est épris. D’ailleurs, c’est pour éterniser ce type de patrimoine et veiller à sa préservation que la vallée du M’zab a pu être inscrite sur la liste des biens communs de l’humanité et classée en secteur sauvegardé. Mais comme partout, en Algérie, la vallée du M’zab n’a pas échappé à la frénésie des constructions qui s’est emparée des agglomérations de ce pays, depuis son Indépendance. Stimulée par une explosion démographique extrêmement forte, cette frénésie a eu des conséquences qui ont grandement éprouvé la vallée du M’zab, d’où un espace urbain transgressé par des extensions qui ne répondent pas à la vocation du site, mais sans toutefois réussir à désagréger la pérennité d’une organisation sociale que le mode de vie a bien préservée. Ces deux aspects ne sont pas susceptibles de disparaître, parce que la société mozabite a conscience que leur présence est le seul gage de son maintien. Évidemment, la conservation de pratiques anciennes ne veut absolument pas dire que cette société répugne à la modernité, car elle y puise ce qui l’aide à être de son temps, et sans avoir à altérer ses valeurs patrimoniales. Ainsi, en voulant résoudre un problème, celui résultant de la crise du logement, la communauté a eu pour stratégie l’adoption d’une nouvelle manière de produire l’urbain, celle qui s’ingénie à perpétuer son patrimoine ancien, qu’il soit matériel ou immatériel, mais en le projetant dans une perspective novatrice reposant sur des pratiques ancrées dans des valeurs séculaires, et en puisant dans la modernité ce qui lui paraît essentiel à ses besoins et à sa durabilité.
Keywords: Monuments -- conservation -- Mzab

انفرادات هود بن محكم الهواري في تفسيره : دراسة تحليلية مقارنة - المنجي, أحمد أحمد محمد (جامعة المنوفية, 2020)
Keywords: Coran -- Commentaires -- 9e siècle; Hawwārī, Hūd b. Muḥkim al-

المسائل المختلف فيها بين المالكية والإباضية في باب العبادات : دراسة تحليلية مقارنة - عثمان, عبد الكريم حسن عبد الكريم (جامعة المنوفية, 2020)
Keywords: Religions comparées -- Ibadisme -- Malékisme

Minorités religieuses et dynamiques identitaires en Tunisie: Ibadites et Juifs à l'épreuve du tourisme et de la révolution - Boussetta, Mourad (Université de Laval, 2020)
Dans cette recherche, j’étudie les dynamiques identitaires des minorités ibadite/berbère et juive de l’île de Djerba (Tunisie) à travers le prisme du tourisme et de la révolution. Je démontre que l’agencéité de ces deux minorités ethnico- religieuses se base sur la force mobilisatrice de leur patrimoine immatériel. Je déconstruis le double discours colonial et national les dotant d’un statut historique et juridique subalterne en me basant sur l’apport critique des études postcoloniales et sur une ethnographie multi-située. J’inscris ce faisant cette agencéité dans une dynamique de relations de pouvoir. J’analyse les adaptations, les négociations et les résistances des acteurs ibadites/berbères et juifs sous le régime colonial puis sous l’État-nation pour aboutir à une meilleure connaissance de leurs stratégies dans l’hyperprésent, soit la révolution de 2011. J’explique qu’en contribuant activement au jumelage de leur patrimoine immatériel à l’industrie touristique et qu’en s’engageant dans la mouvance politique postrévolutionnaire, ces acteurs se réapproprient une citoyenneté entière en Tunisie. Cet examen critique met en évidence les stratégies adoptées par les acteurs des minorités étudiées pour se repositionner par rapport aux structures, non pas dans le sens d’une rupture, mais plutôt dans celui de s’insérer dans les relations de pouvoir avec un statut avantageux.
Keywords: Judaïsme -- Djerba; Tourisme -- Djerba

Omani Ibadism: Guide to a peace-seeking foreign policy? - Hooghwinkel, Jasper (Leiden University, 2020)

The Halachic Approach of Rabbi Moshe Chalfon Ha'kohen From Djerbah As it Reflected in his Halachic writings- 'Brit Kehuna' And the Responsa 'Shoel V'Nishal' - Mamo, Shai (Universität Potsdam, 2020)
This work is focused on the Halachic Approach of Rabbi Moshe Chalfon HaCohen from Djerbah. Rabbi Moshe Chalfon HaCohen was born in 1874 and died 1950. He was appointed Chief Rabbi of Djerbah, an island near Tunisia, in 1935, and is considered to have been one of the greatest rabbis of North Africa, particularly of Tunisia and Djerbah. With the French occupation of Tunisia in 1881, French culture, technological innovations and modernity penetrated the community. All of these affected life in Djerbah and the rabbis, including Rabbi Chalfon, needed to relate to this new situation. This research deals with two of Rabbi Chalfon’s essays dealing with Halachic responsa: “Brit Kehuna” – a compilation of the Halachic responsa and customs of the Jewish community in Djerbah, and “Shoel Venishal,” a book of Halachic responsa which deals with questions and his answers. Among other aspects, this research shows Rabbi Chalfon's unique emphasis on the humane aspects of Halacha and his ability to utilize them versus formal considerations.
Keywords: Judaïsme -- Djerba

Ibaḍi Modernism and the Omani nahḍa of 1913 - Barber, Christopher (Leiden University, 2020)
This thesis examines the Ibadi nahda of 1913 through an Islamic Modernist framing to show links between the Ibadi revival and a wider pan-Islamist and anti-colonial moment. The main focus are the writings of Nur al-Din al-Salimi (d. 1914) and Abu Muslim al-Bahlani (d. 1920), two luminaries and revolutionaries of the Ibadi revival movement. An 'episodic discourse' model of ideology production is used to relate the social and material conditions of turn of the century colonial Zanzibar and Oman to modernist religious discourse.
Keywords: Vie politique -- Oman -- 1913-1932

L’organisation territoriale de l’île de Djerba du XIIe au XVIe siècle, à la croisée des sources musulmanes et latines - Salah, Karim (Université Lumière Lyon 2, 2020)
Ce présent travail se penche sur l’Histoire du peuplement et de la gestion des ressources naturelles, ainsi que de l’organisation territoriale de l’île de Djerba entre le XIIe et le XVIe siècle, au travers des sources médiévales et modernes musulmanes et latines. Il sera mesuré l’impact des événements historiques et de l’environnement sur le paysage insulaire, comment elle façonne les spécificités de Djerba, et son insertion dans l’espace méditerranéen.
Keywords: Urbanisme -- Djerba

The Expansion of Christianity in the Pre-Islamic Middle East: from Edessa to 'Uman - Atchison-Day, Susan (University of Arizona, 2020)
Keywords: Christianisme -- Oman